aerogel complex

JP2026536489APending Publication Date: 2026-10-30LG CHEM LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026520483
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-02-07
Filing Date
2024-10-04
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

【0032】 本発明で提供するエアロゲル複合体は、それをバッテリ、電子機器、自動車、産業機器、または構造物などに断熱材として適用する際、隣り合って位置する各種機器や構造物の膨張やその他の原因でエアロゲル複合体に圧力が加えられて圧縮変形されても断熱性が大きく低下せず、優れた水準で維持され得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026536489000001_ABST
    Figure 2026536489000001_ABST
Patent Text Reader

Abstract

This invention relates to an aerogel composite that maintains excellent thermal insulation properties even when subjected to compression and deformation due to pressure applied by various causes when applied as a thermal insulation material to batteries, electronic devices, automobiles, industrial equipment, or structures.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] Mutual citation with related applications (etc.) This application claims priority under Korean Patent Application No. 10-2023-0132930 dated October 5, 2023, and U.S. Patent Application No. 18 / 435,481 dated February 7, 2024, and all content disclosed in the relevant Korean patent applications is incorporated herein by reference.

[0002] This invention relates to aerogel composites and their applications as thermal insulation materials. [Background technology]

[0003] Aerogel is a highly porous material with a porosity of approximately 90.0% to 99.9% and a pore size in the range of 1 nm to 100 nm, resulting in a high specific surface area (≥500 m²). 2 Aerogel is a substance that possesses excellent properties such as being ultralight, ultra-thermal, and ultra-low dielectric. Therefore, in addition to research and development of aerogel materials, active research and application studies are being conducted on its use as a transparent thermal insulation material, an environmentally friendly high-temperature thermal insulation material, an ultra-low dielectric thin film for highly integrated devices, a catalyst and catalyst support, an electrode for supercapacitors, and an electrode material for seawater desalination.

[0004] The greatest advantages of aerogel are its super-insulation properties, exhibiting a thermal conductivity of less than 0.300 W / m·K, which is lower than conventional organic insulation materials such as expanded polystyrene, and its ability to overcome the fatal weaknesses of organic insulation materials: their vulnerability to fire and the generation of harmful gases during a fire.

[0005] Generally, aerogels are manufactured by producing a hydrogel from a silica precursor such as water glass or alkoxysilane (TEOS, TMOS, MTMS, etc.), and then removing the liquid component inside the hydrogel without destroying its microstructure.

[0006] In particular, hydrophobic silica aerogel blankets, which have hydrophobic silica aerogel formed on fibers, are functional thermal insulation materials that prevent corrosion due to moisture and are widely used in construction and industrial sites. They can also be useful as thermal insulation, heat retention, or fire-resistant materials for aircraft, ships, automobiles, batteries, and other applications.

[0007] However, when applying such silica aerogel blankets to the aforementioned applications, there was a problem in that the thermal insulation performance was significantly reduced due to a pressurized environment caused by continuous thermal expansion from adjacent equipment, or due to the collapse of the aerogel structure caused by significant pressure being applied from the surroundings during the installation of the aerogel insulation material. [Overview of the project] [Problems that the invention aims to solve]

[0008] One objective of the present invention is to provide an aerogel composite or a thermal insulation member containing the same that can maintain a constant thermal insulation performance without a significant decrease even when exposed to a pressurized environment.

[0009] However, the technical problems that this invention aims to solve are not limited to those mentioned above. Other problems not mentioned should be clearly understood by those with ordinary knowledge in this industry from the following description. [Means for solving the problem]

[0010] According to one embodiment of the present invention, the present invention relates to an aerogel composite comprising a fibrous substrate and an aerogel having a plurality of open pores, wherein the aerogel contains a plurality of silica aerogel particles, and in a small-angle X-ray scattering (SAXS) graph showing the scattering intensity with respect to wave number logarithmically for the aerogel particles, the slope in the wave number range of 0.015 / Å to 0.035 / Å is -2.80 to -2.20.

[0011] The small-angle X-ray scattering graph may be for the aerogel particles desorbed from the aerogel composite.

[0012] The small-angle X-ray scattering graph may be for the aerogel particles within the aerogel composite.

[0013] When the cross section of the aerogel composite is compressed by applying pressures of 3 bar, 9 bar, and 24 bar in the horizontal direction (transverse direction), the heat transmission coefficient after compression may be 1.8 times or less of the heat transmission coefficient before compression.

[0014] When the cross section of the aerogel composite is compressed by applying pressures of 3 bar, 9 bar, and 24 bar in the horizontal direction (transverse direction), the heat transmission coefficient after compression may be more than 1 time and 1.8 times or less of the heat transmission coefficient before compression.

[0015] For the aerogel composite, the heat transmission coefficients before and after compression may satisfy the following Equation 4: [Equation 4] {(Heat transmission coefficient before and after compression (a)) - (Average value (b) of heat transmission coefficients before and after compression)} = (Average value (b) of heat transmission coefficients before and after compression) × A

[0016] In Equation 4, the heat transmission coefficient before and after compression (a) means the heat transmission coefficient obtained after compressing the cross section of the aerogel composite at 0 bar, 3 bar, 9 bar, or 24 bar in the horizontal direction (transverse direction), the average value (b) of heat transmission coefficients before and after compression means the average value of the heat transmission coefficient of the unpressurized aerogel composite and the heat transmission coefficients obtained after compressing the cross section of the aerogel composite at compression values of 3 bar, 9 bar, and 24 bar in the horizontal direction (transverse direction), and A is a real number from -0.40 to +0.40.

[0017] For the aerogel composite, the heat transmission coefficients before and after compression may satisfy the following Equation 4: [Equation 4] {(Heat transmission coefficient before and after compression (a)) - (Average value (b) of heat transmission coefficients before and after compression)} = (Average value (b) of heat transmission coefficients before and after compression) × A In Equation 4 above, the thermal transmittance before and after compression (a) refers to the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) at 0 bar, 3 bar, or 9 bar relative to the cross-section, and the average value of the thermal transmittance before and after compression (b) refers to the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) at compression values ​​of 0 bar, 3 bar, and 9 bar relative to the cross-section, where A is a real number between -0.23 and +0.23.

[0018] The thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) at pressures of 3 bar, 9 bar, and 24 bar relative to its cross-section can satisfy the following equation 5: [Formula 5] {(Compressed heat transfer coefficient (c) - Average heat transfer coefficient after compression (d))} = (Average heat transfer coefficient after compression (d)) × B

[0019] In equation 5, the thermal transmittance after compression (c) refers to the thermal transmittance obtained after compressing the aerogel composite with a pressure of 3 bar, 9 bar, or 24 bar in the horizontal direction (lateral direction) relative to the cross-section of the aerogel composite, the average value of the thermal transmittance after compression (d) refers to the average value of the thermal transmittance obtained after compressing the aerogel composite with pressures of 3 bar, 9 bar, and 24 bar applied in the horizontal direction (lateral direction) relative to the cross-section of the aerogel composite, and B is a real number between -0.30 and +0.30.

[0020] For the aerogel composite, the rate of change (C) of the thermal transmittance after compression per unit applied pressure, expressed by the following formula 6, can be a real number between -0.15 and +0.15: [Formula 6] C = {(thermal transmittance after compression at pressure x - thermal transmittance after compression at pressure y)} / (xy) In equation 6 above, x and y are either 3 bar or 24 bar independently, or they are different pressure values ​​from each other.

[0021] When pressures of 3 bar, 9 bar, and 24 bar are applied horizontally (laterally) to the cross-section of the aerogel composite, the compression recovery force expressed by the following formula 2 may be 60% or more: [Formula 2] Compression recovery force (%) = {(thickness of the cross-section of the aerogel composite after compression) / (thickness of the cross-section of the aerogel composite before compression)} × 100

[0022] The aerogel may contain pores with a pore diameter of 30 nm or less, accounting for 30% to 45% of the pore volume of the skeletal structure.

[0023] The aerogel may consist of silica, methylsilylated silica, dimethylsilylated silica, trimethylsilylated silica, or a mixture thereof.

[0024] The aerogel particles may include particles in which multiple aerogel particles with a particle size greater than 0 and less than or equal to 5 nm are aggregated or bound together.

[0025] The average particle size of the aggregated or bound particles may be between 5 and 2,000 nm.

[0026] The fiber substrate may include one or more selected from the group consisting of polyester, polyolefin terephthalate, poly(ethylene) naphthalate, polycarbonate, cotton, carbon, polyacrylonitrile (PAN), oxidized PAN, non-carbonized heat-treated PAN, glass fiber, silica fiber, polyaramid fiber, polyolefin fiber, fluoropolymer fiber, silicon carbide fiber, ceramic paper, ceramic fiber, acrylic polymer fiber, basalt fiber, wool, silk, hemp, leather, suede fiber, PBO-Zylon fiber (manufactured by TOYOBO), liquid crystal fiber, polyurethane fiber, polyamide fiber, wool fiber, boron, aluminum, iron, stainless steel fiber, or PEEK, PES, PET, PEK, and PPS.

[0027] The thickness of the aerogel composite may be 0.5 mm to 20 mm.

[0028] The density of the aerogel composite is 0.05 to 0.50 g / cm³. 3It is possible.

[0029] The aerogel composite has a compressive strength of 20 kPa to 80 kPa at 10% deformation and a tensile strength of 30 N / cm². 2 ~60N / cm 2 It is possible.

[0030] Another embodiment of the present invention relates to a thermal insulation member comprising an aerogel composite provided in the present invention.

[0031] The thermal insulation member may further include a support member located on at least one of the upper and lower surfaces of the aerogel composite. [Effects of the Invention]

[0032] The aerogel composite provided in this invention, when applied as an insulating material to batteries, electronic devices, automobiles, industrial equipment, or structures, maintains an excellent level of thermal insulation even when pressure is applied to the aerogel composite due to expansion of adjacent equipment or structures or other causes, resulting in compression deformation. [Brief explanation of the drawing]

[0033] [Figure 1] This figure shows the aerogel powder (particles) detached from the aerogel composites of Examples 1 and 3 in Experimental Example 2, and a graph of the small-angle X-ray diffraction (SAXS) analysis results for the aerogel composite of Example 1. [Figure 2] This figure shows graphs obtained by small-angle X-ray diffraction (SAXS) analysis of aerogel powder (particles) detached from the aerogel composites of Comparative Examples 1 and 2 in Experimental Example 2. [Modes for carrying out the invention]

[0034] According to one embodiment of the present invention, the present invention relates to an aerogel composite comprising a fibrous substrate and an aerogel having a plurality of open pores, wherein the aerogel comprises a plurality of silica aerogel particles, and in a small-angle X-ray scattering (SAXS) graph showing the scattering intensity with respect to wavenumber logarithmically for the silica aerogel particles, the slope in the wavenumber range of 0.015 / Å to 0.035 / Å is -2.80 to -2.20.

[0035] The small-angle X-ray scattering graph may be for silica aerogel particles detached from the aerogel composite.

[0036] The small-angle X-ray scattering graph may be for silica aerogel particles within the aerogel composite.

[0037] When the aerogel composite is compressed horizontally (laterally) to 3 bar, 9 bar, and 24 bar relative to its cross-section, the thermal transmittance after compression may be 1.8 times or less compared to the thermal transmittance before compression.

[0038] When the aerogel composite is compressed horizontally (laterally) to 3 bar, 9 bar, and 24 bar relative to its cross-section, the thermal transmittance after compression may be more than 1 and less than or equal to 1.8 times the thermal transmittance before compression.

[0039] For the aerogel composite, the thermal transmittance before and after compression can satisfy the following equation 4: [Formula 4] {(Thermal transmittance before and after compression (a)) - (Average thermal transmittance before and after compression (b))} = (Average thermal transmittance before and after compression (b)) × A

[0040] In Equation 4 above, the thermal transmittance before and after compression (a) refers to the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) at 0 bar, 3 bar, 9 bar, or 24 bar relative to the cross-section of the aerogel composite, and the average value of the thermal transmittance before and after compression (b) refers to the thermal transmittance of the unpressurized aerogel composite and the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) at compression values ​​of 3 bar, 9 bar, and 24 bar relative to the cross-section of the aerogel composite, where A is a real number between -0.40 and +0.40.

[0041] For the aerogel composite, the thermal transmittance before and after compression can satisfy the following equation 4: [Formula 4] {(Thermal transmittance before and after compression (a)) - (Average thermal transmittance before and after compression (b))} = (Average thermal transmittance before and after compression (b)) × A

[0042] In Equation 4 above, the thermal transmittance before and after compression (a) refers to the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) at 0 bar, 3 bar, or 9 bar relative to the cross-section of the aerogel composite, and the average value of the thermal transmittance before and after compression (b) refers to the average value of the thermal transmittance of the aerogel composite without pressure and the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) at compression values ​​of 3 bar and 9 bar relative to the cross-section of the aerogel composite, where A is a real number between -0.23 and +0.23.

[0043] The thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) at pressures of 3 bar, 9 bar, and 24 bar relative to its cross-section can satisfy the following equation 5: [Formula 5] {(Compressed heat transfer coefficient (c) - Average heat transfer coefficient after compression (d))} = (Average heat transfer coefficient after compression (d)) × B

[0044] In equation 5, the thermal transmittance after compression (c) refers to the thermal transmittance obtained after compressing the aerogel composite with a pressure of 3 bar, 9 bar, or 24 bar in the horizontal direction (lateral direction) relative to the cross-section of the aerogel composite, the average value of the thermal transmittance after compression (d) refers to the average value of the thermal transmittance obtained after compressing the aerogel composite with pressures of 3 bar, 9 bar, and 24 bar applied in the horizontal direction (lateral direction) relative to the cross-section of the aerogel composite, and B is a real number between -0.30 and +0.30.

[0045] For the aerogel composite, the rate of change (C) of the thermal transmittance after compression per unit applied pressure, expressed by the following formula 6, can be a real number between -0.15 and +0.15: [Formula 6] C = {(thermal transmittance after compression at pressure x - thermal transmittance after compression at pressure y)} / (xy)

[0046] In equation 6 above, x and y are either 3 bar or 24 bar independently, or they are different pressure values ​​from each other.

[0047] When pressures of 3 bar, 9 bar, and 24 bar are applied horizontally (laterally) to the cross-section of the aerogel composite, the compression recovery force expressed by the following formula 2 may be 60% or more: [Formula 2] Compression recovery force (%) = {(thickness of the cross-section of the aerogel composite after compression) / (thickness of the cross-section of the aerogel composite before compression)} × 100

[0048] The aerogel may contain pores with a pore diameter of 30 nm or less, accounting for 30% to 45% of the pore volume of the skeletal structure.

[0049] The aerogel may consist of silica, methylsilylated silica, dimethylsilylated silica, trimethylsilylated silica, or a mixture thereof.

[0050] The silica aerogel particles may include particles in which multiple aerogel particles with a particle size greater than 0 and less than or equal to 5 nm are aggregated or bonded together.

[0051] The average particle size of the aggregated or bound particles may be between 5 and 2,000 nm.

[0052] The aforementioned fibrous substrate may contain glass fibers.

[0053] The thickness of the aerogel composite may be 0.5 mm to 20 mm.

[0054] The density of the aerogel composite is 0.05 to 0.50 g / cm³. 3 It is possible.

[0055] The aerogel composite has a compressive strength of 20 kPa to 80 kPa at 10% deformation and a tensile strength of 30 N / cm². 2 ~60N / cm 2 It is possible.

[0056] Another embodiment of the present invention relates to a thermal insulation member comprising an aerogel composite provided in the present invention.

[0057] The thermal insulation member may further include a support member located on at least one of the upper and lower surfaces of the aerogel composite.

[0058] The present invention will be described in more detail below to aid in understanding the invention. In this regard, terms and words used herein and in the claims should not be interpreted only in their ordinary or dictionary sense, but should be interpreted in a sense and concept that is consistent with the technical idea of ​​the present invention, based on the principle that inventors can appropriately define the concepts of terms in order to best describe their invention.

[0059] According to one embodiment of the present invention, the present invention relates to an aerogel composite comprising a fibrous substrate and an aerogel containing a plurality of open pores.

[0060] The aforementioned "aerogel" contains a plurality of primary aerogel particles having a size of approximately 0 or greater than 10 nm and 0 or greater than 5 nm, and secondary aerogel particles formed by the aggregation or bonding of such primary aerogel particles. Multiple open pores are formed between the primary aerogel particles and between the secondary aerogel particles, forming aggregates, thereby giving the aerogel a three-dimensional network structure.

[0061] The aerogel may be an inorganic silica aerogel made from a silicon alkoxide compound or water glass as a precursor. For example, the aerogel may consist of silica, methylsilylated silica, dimethylsilylated silica, trimethylsilylated silica, or a mixture thereof. As another example, the aerogel may have at least some of the SiO2 on the surface of the SiO2 network structure having a Si-O-SiO2(CH3), Si-O-SiO(CH3)2, or Si-O-Si(CH3)3 bond structure. The specific manufacturing process for silica aerogels is described in detail below.

[0062] Aerogel particles may be located on the fibrous substrate and in the voids between adjacent fibrous substrates. The "aerogel particles" are individual solid units that make up the aerogel and may include both primary aerogel particles having a size of approximately 0 to 10 nm or less, or 0 to 5 nm or less, preferably around 1 nm, and secondary aerogel particles formed by the aggregation of these particles. However, the aerogel in the aerogel composite is mostly in the form of secondary aerogel particles or aggregated and bound forms thereof, and a small amount of primary aerogel particles that do not form secondary aerogel particles may be present. The average particle size of the secondary aerogel particles may be approximately 5 to 2,000 nm, 5 to 1,000 nm, 5 to 500 nm, 5 to 100 nm, or 5 to 50 nm, but is not limited thereto. The size of the particles may be measured by any means known to those skilled in the art, such as scanning electron microscopy, dynamic light scattering, optical microscopy, or size exclusion methods, but is not limited thereto.

[0063] Generally, aerogel particles (secondary aerogel particles) can be manufactured in various shapes such as disc-shaped, spherical, cocoon-shaped, rod-shaped, or amorphous. However, the aerogel composite provided in this invention contains a high proportion of oblate disc-shaped secondary aerogel particles, which are disc-shaped with a bulging central portion. This increases the processing ratio within the aerogel composite, improving both the strength and elastic recovery rate of the aerogel's three-dimensional network structure. As a result, when the aerogel composite is applied as an insulating material to battery modules and the like, it can maintain excellent recovery and insulation properties even when compressed due to expansion of surrounding equipment.

[0064] In connection with this, small-angle X-ray scattering (SAXS) analysis was performed to analyze the structural characteristics of the aerogel particles of the present invention.

[0065] The aforementioned "small-angle X-ray scattering (SAXS)" is an analytical method that obtains structural information about a material by irradiating it with X-rays and measuring the scattered X-rays at a small scattering angle. This is achieved by analyzing the elastic scattering behavior of X-rays as they pass through the material and recording the scattering at a small angle (generally 0.1 to 10°, hence the name "small angle"). This belongs to the small-angle scattering (SAS) technique series along with small-angle neutron scattering and is generally performed using hard X-rays with wavelengths of 0.07 to 0.2 nm. Due to the angular range in which clear scattering signals can be recorded, SAXS can provide structural information in size from 1 to 100 nm and repeatability distances of partially aligned systems up to 150 nm.

[0066] Furthermore, the "small-angle X-ray scattering (SAXS)" graph shows the wavenumber dependence of the scattering intensity I (intensity) in the range where the scattering angle 2θ is 10° or less, among the scattered X-rays that are incident on an aerogel composite or aerogel particles and scattered by the aerogel particles. The scattering angle 2θ can be adjusted by the separation distance between the sample and the detector. The small-angle X-ray scattering graph is expressed as scattering intensity I against wavenumber Q (unit: Å-1), where wavenumber Q is calculated from 4πsinθ / λ, and λ represents the wavelength of the X-rays.

[0067] Small-angle X-ray scattering (SAXS) analysis of the aerogel composite of the present invention, preferably the aerogel particles contained in the aerogel composite, yields a graph showing the scattering intensity logarithmically with respect to wavenumber. In such a graph, the slope in the wavenumber range of 0.015 / Å to 0.035 / Å is characterized by being -2.80 to -2.20, -2.70 to -2.20, -2.60 to -2.20, -2.55 to -2.20, or -2.50 to -2.20. In this case, the slope is shown by calculating the change in scattering intensity due to wavenumber change in a linear regression obtained using the least squares method in the wavenumber range of 0.015 / Å to 0.035 / Å. As an example, in the graph, the slope in the wavenumber range of 0.015 / Å to 0.035 / Å may be -2.80 to -2.20.

[0068] Figure 1 shows a logarithmic graph of scattering intensity against wavenumber obtained by small-angle X-ray scattering (SAXS) analysis of aerogel powder (aerogel particles) or aerogel composite detached from an aerogel composite according to one experimental example of the present invention. It can be seen that the aerogel particles or aerogel composite containing them according to the present invention have a slope in the range of -2.80 to -2.20 in the wavenumber range of 0.015 / Å to 0.035 / Å.

[0069] The aerogel composite according to the present invention contains a higher proportion of secondary aerogel particles having a flattened spherical structure compared to conventional aerogel composites, and the absolute value of the gradient in the wavenumber range of 0.015 / Å to 0.035 / Å of the small-angle X-ray scattering (SAXS) graph is larger than that of conventional aerogel composites. For the reasons mentioned above, the aerogel composite according to the present invention has a high proportion of voids, and as will be described later, it has the characteristics of high strength, elastic recovery rate, and compressive recovery rate in the three-dimensional network structure of the aerogel, and the thermal transmittance after compression does not increase significantly.

[0070] The small-angle X-ray scattering (SAXS) analysis described above can be performed on the aerogel composite provided in the present invention or on aerogel powder (aerogel particles) detached from the aerogel composite. In this case, when the small-angle X-ray scattering (SAXS) analysis is performed on the aerogel composite, the small-angle X-ray scattering (SAXS) graph obtained from the analysis may substantially represent aerogel particles contained within the aerogel composite that are attached to or bound to the fibrous substrate or contained within the aerogel network structure.

[0071] As an example, a small-angle X-ray scattering (SAXS) graph may be obtained as a result of small-angle X-ray scattering (SAXS) analysis performed on aerogel powder (aerogel particles) detached from an aerogel composite.

[0072] In this case, the aerogel powder may be obtained from a rectangular aerogel composite (for example, it may be, but is not limited to, a rectangular aerogel composite with dimensions of 60 cm x 12 cm), or from a fragment of a sample obtained by cutting a portion of the composite.

[0073] The aerogel powder used for the small-angle X-ray scattering (SAXS) analysis can be prepared by the following process: An aerogel composite measuring 60 cm x 12 cm was placed in a sealed container and repeatedly shaken up and down to induce desorption of the aerogel powder. To remove the fibrous substrate mixed in with the desorbed aerogel powder, the fibrous substrate visible to the naked eye was first removed with tweezers. Next, the aerogel powder was placed in a 100 ml vial, and distilled water was added at a weight ratio of approximately 1:130 (powder:distilled water), followed by 50 violations. This removed the fibrous substrate settled at the bottom of the vial and the aggregates formed by the solidification of the fibrous substrate and aerogel powder, allowing only the aerogel powder floating in the upper layer of distilled water to be carefully collected. The collected aerogel powder was dried at 120°C for 1 hour and used in the experiment of the present invention. At this time, at least 10 mg of the final collected aerogel powder sample is required for sufficient analysis.

[0074] As an example, a small-angle X-ray scattering (SAXS) graph may be obtained as a result of performing small-angle X-ray scattering (SAXS) analysis on a sample of an aerogel composite. In this case, the sample may be a square with dimensions of 1 cm x 1 cm. In the present invention, when performing small-angle X-ray scattering (SAXS) analysis on a sample of an aerogel composite as described above, the slope of the small-angle X-ray scattering (SAXS) graph may be shown as the average value of the slopes measured in a wavenumber range of 0.015 / Å to 0.035 / Å from the graphs obtained for each sample after performing small-angle X-ray scattering (SAXS) analysis on all five samples obtained from the same aerogel composite. In this process, five specimens are obtained by preparing a rectangular aerogel composite (for example, with dimensions of 60 cm x 12 cm, but not limited to this size) such that the center of the specimen is located 10 cm away from each corner toward the center, and one specimen is obtained such that the center portion of the aerogel composite is located in the center of the specimen.

[0075] As an example, the small-angle X-ray scattering (SAXS) graph is obtained from the results of small-angle X-ray scattering (SAXS) analysis of aerogel powder detached from the aerogel composite of the present invention, and the slope in the wavenumber range of 0.015 / Å to 0.035 / Å may be -2.80 to -2.20, -2.70 to -2.20, or -2.60 to -2.20.

[0076] As an example, the small-angle X-ray scattering (SAXS) graph is obtained from the results of small-angle X-ray scattering (SAXS) analysis of aerogel powder contained in the aerogel composite or a portion thereof of the present invention, and the slope in the wavenumber range of 0.015 / Å to 0.035 / Å may be -2.80 to -2.20, -2.70 to -2.20, or -2.60 to -2.20.

[0077] The aforementioned small-angle X-ray scattering (SAXS) analysis was performed by transmitting X-rays through a sample using a Xenocs Xeuss2.0 X-ray scattering system and measuring the scattering intensity I(q) based on the scattering wavenumber Q. More specifically, the SAXS analysis was performed by placing the sample 2.5 m away from the detector and incident X-rays onto it. A Pilatus3 300K (2D detector) was used as the detector. The resulting 2D diffraction pattern was obtained as an image, and this was calibrated using the sample-to-detector distance obtained with a standard sample. Next, the 2D circuit pattern obtained from the specimen analysis was used for circular averaging to convert the scattering intensity I(q) based on the scattering wavenumber Q. [Formula 1] Q = 4πsinθ / λ

[0078] In the above general formula 1, Q is the scattering wavenumber (vector), θ is half the scattering angle, and λ is the wavelength of the irradiated X-rays.

[0079] Aerogel composites possessing the aforementioned characteristics exhibit excellent elasticity and flexibility, and even when compressed and deformed under pressure, they exhibit superior elastic recovery and can maintain a high level of thermal insulation.

[0080] The aerogel may have a skeletal structure that includes mesopores, but may also include micropores or macropores in addition to the mesopores. Here, "mesopores" are pores with an average pore diameter in the range of approximately 2 nm to approximately 50 nm, "macropores" are pores with an average pore diameter exceeding approximately 50 nm, and "micropores" are pores with an average pore diameter of less than approximately 2 nm. The aerogel may contain at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95%, at least 96%, at least 97%, at least 98%, at least 99%, or 100% mesopores of the pore volume of the skeletal structure. In one specific example, the aerogel of the present invention may contain mesopores. In one specific example, the aerogel of the present invention may contain both mesopores and micropores. The size of the pores can be measured by any means known to those skilled in the art, such as gas adsorption experiments, mercury infiltration, capillary flow porometry, or positron annihilation lifetime spectroscopy (PALS), but is not limited to these.

[0081] In aerogels, pores with a diameter of 30 nm or less are not destroyed or undergo only minor destruction even when the aerogel is compressed under high pressure (for example, at pressures of 37 bar or less, 33 bar or less, or 30 bar or less). Therefore, in this invention, by ensuring that a certain proportion of pores with a diameter of 30 nm or less are included in the aerogel, the thermal transmittance of the aerogel composite can be maintained within a certain range compared to before pressurization, even under a pressurized environment.

[0082] More specifically, the aerogel may contain pores with a pore diameter greater than 0 and less than or equal to 30 nm in 25% or more, 26% or more, 27% or more, 28% or more, 29% or more, 30% or more, or 31% or more of the pore volume of the skeletal structure, and may contain 50% or less, 49% or less, 48% or less, 47% or less, 46% or less, 45% or less, 44% or less, 43% or less, 41% or less, or 40% or less, preferably 25% or more and 45% or less, 25% or more and 40% or less, 30% or more and 45% or less, 30% or more and 40% or less, more preferably 30% or more and 45% or less, or 30% or more and 40% or less. As an example, pores with a pore diameter greater than 0 and less than or equal to 30 nm may contain 30% or more and 45% or less of the pore volume of the skeletal structure.

[0083] Furthermore, the aerogel may contain pores with a pore diameter exceeding 30 nm in amounts of 50% or more, 51% or more, 52% or more, 53% or more, 54% or more, 55% or more, 56% or more, 57% or more, 58% or more, 59% or more, or 60% or more of the pore volume of the skeletal structure, and may contain 75% or less, 74% or less, 73% or less, 72% or less, 71% or less, 70% or less, or 69% or less, preferably 55% or more and 75% or less, 60% or more and 75% or less, 55% or more and 70% or less, 60% or more and 70% or less, more preferably 55% or more and 70% or less, or 60% or more and 70% or less.

[0084] The porosity of the aerogel may be 80% or more, 85% or more, 88% or more, 89% or more, 90% or more, 91% or more, 93% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more, preferably 80% or more and 99.9% or less, but is not limited to these values.

[0085] The aerogel composite has a structure in which at least a portion of a plurality of aerogel particles are dispersed, preferably bound, on the surface of a fiber-containing substrate, and at the same time, at least a portion of the plurality of aerogel particles are dispersed, preferably located, in the spaces between the fibers dispersed within the substrate. Examples of the substrate may include discrete fibers, films, sheets, nets, fibers, porous materials, foams, nonwoven fabrics, or laminates of two or more layers thereof. Depending on the application, the surface may also have surface roughness or a patterned surface.

[0086] The aforementioned fiber base materials include polyester, polyolefin terephthalate, poly(ethylene) naphthalate, polycarbonate (e.g., rayon, nylon), cotton (e.g., Lycra® manufactured by DuPont), carbon (e.g., graphite), polyacrylonitrile (PAN), PAN oxide, non-carbonized heat-treated PAN (e.g., those made of SGL carbon), glass fiber materials (S-glass, 901 glass, 902 glass, 475 glass, E-glass, etc.), silica-based fibers, such as quartz (e.g., Quartz manufactured by Saint-Gobain). tzel®, Q-Fiber® felt (manufactured by Johns Manville), Saffil (manufactured by Safil), Durablanket (manufactured by Uniflac), and other silica fibers, Duraback® (manufactured by Carborundum), polyaramid fibers such as Kevlar®, Nomex®, Sontera® (manufactured by DuPont), Conex (manufactured by Teijin), polyolefins such as Tyvek® (manufactured by DuPont), Dyneema® (registered trademark). Trademarks) (manufactured by DSM), Spectra (registered trademark) (manufactured by Honeywell), other polypropylene fibers, e.g., Typar (registered trademark), Xavan (registered trademark) (both manufactured by DuPont), fluoropolymers, e.g., PTFE under the trademark name Teflon (registered trademark) (manufactured by DuPont), Goretex (registered trademark) (manufactured by WLGORE), silicon carbide fibers, e.g., Nicalcon (manufactured by COI Ceramics), ceramic paper, ceramic fibers, e.g., Nextel (manufactured by 3M), acrylic polymers, The fiber base material may include basalt fibers, wool, silk, hemp, leather, suede fibers, PBO-Zylon® fibers (manufactured by TOYOBO), liquid crystal materials such as Vectan (manufactured by Hoechst), Cambrelle fibers (manufactured by DuPont), polyurethane, polyamide, wool fibers, boron, aluminum, iron, stainless steel fibers, or other thermoplastic resins such as PEEK, PES, PET, PEK, and PPS, but is not limited to any fiber that can further improve thermal insulation performance by containing spaces or voids that facilitate the insertion of aerogel. As an example, the fiber base material may consist of glass fibers.

[0087] The thickness of the fibrous base material may be 0.5 to 20 mm, but is not limited thereto.

[0088] The density of the aerogel composite is 0.05 to 0.50 g / cm 3 , 0.05 to 0.35 g / cm 3 , 0.05 to 0.30 g / cm 3 , 0.10 to 0.30 g / cm 3 , or 0.15 to 0.30 g / cm 3 , but is not limited thereto.

[0089] As described above, the aerogel composite provided by the present invention is excellent in both elasticity and flexibility, and even when the aerogel composite is compressively deformed under a pressurized environment, it has excellent elastic recovery force, and the thermal insulation property can be maintained at a high level.

[0090] When a pressure of 1 bar or more, 2 bar or more, 3 bar or more, 4 bar or more, 5 bar or more, 6 bar or more, 7 bar or more, 8 bar or more, 9 bar or more, 10 bar or more, 15 bar or more, 20 bar or more, 25 bar or more, 30 bar or more, 35 bar or more, or 40 bar or more, and 50 bar or less, 45 bar or less, 40 bar or less, 35 bar or less, 30 bar or less, 25 bar or less, 20 bar or less, 15 bar or less, 10 bar or less, 9 bar or less, 8 bar or less, 7 bar or less, 6 bar or less, 5 bar or less, 4 bar or less, 3 bar or less, or 2 bar or less is applied in the horizontal direction (transverse direction) relative to the cross section of the aerogel composite, the compression recovery rate may be 45% or more, 50% or more, 55% or more, 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more. As an example, the compression recovery rate may be 60% or more.

[0091] The term "compression recovery force" refers to the percentage of the thickness of the cross-section of the aerogel composite after a predetermined time has elapsed since compression relative to the thickness of the cross-section of the aerogel composite before compression, as shown in Equation 2 below. Here, the predetermined time may be, but is not limited to, 1 second or more, 5 seconds or more, 10 seconds or more, 30 seconds or more, 1 minute or more, 5 minutes or more, 10 minutes or more, 20 minutes or more, 30 minutes or more, 40 minutes or more, 50 minutes or more, 1 hour or more, 2 hours or more, 4 hours or more, 6 hours or more, 8 hours or more, 10 hours or more, 12 hours or more, 24 hours or more, 48 hours or more, or 96 hours or more. As an example, the post-compression recovery rate may be measured 60 minutes (1 hour) after the aerogel composite has been compressed. [Formula 2] Compression recovery force (%) = {(thickness of the cross-section of the aerogel composite after compression) / (thickness of the cross-section of the aerogel composite before compression)} × 100

[0092] The aforementioned "pressure" value refers to the pressure applied per unit area of ​​the aerogel composite when pressure is applied horizontally (laterally) to the cross-section of the aerogel composite using a press machine or the like. As an example, when pressure is applied horizontally (laterally) to the cross-section of the aerogel composite using a press machine including a cylinder, the effective pressure value may mean the product of the cross-sectional area of ​​the cylinder and the set pressure value divided by the area of ​​the specimen, as shown in Equation 3 below. However, it is not limited to this and may be calculated differently depending on the equipment or the manufacturer. [Formula 3] Actual pressure value = (radius of the cylinder inner diameter of the press equipment (cm) × radius of the cylinder inner diameter of the press equipment (cm) × 3.14 × set pressure value) / (area of ​​the test piece (cm) 2 ))

[0093] Applying a horizontal (lateral) direction to the cross-section of the aerogel composite means applying pressure to the aerogel composite in the direction from the top surface to the bottom surface or from the bottom surface to the top surface, that is, in the thickness direction.

[0094] The duration for which pressure is applied to the aerogel composite is not particularly limited, but may be, for example, 1 second or more, 5 seconds or more, 10 seconds or more, 30 seconds or more, 1 minute or more, 5 minutes or more, 10 minutes or more, 20 minutes or more, 30 minutes or more, 40 minutes or more, 50 minutes or more, 1 hour or more, or 2 hours or more, and 24 hours or less, 12 hours or less, 10 hours or less, 8 hours or less, 6 hours or less, 4 hours or less, 2 hours or less, 1 hour or less, 50 minutes or less, 40 minutes or less, 30 minutes or less, 20 minutes or less, 10 minutes or less, 5 minutes or less, 1 minute or less, 30 seconds or less, or 5 seconds or less, but is not limited to these. As an example, the duration for which pressure is applied may be 10 minutes.

[0095] As an example, when a pressure of 3 bar, 9 bar, 15 bar, 24 bar, 30 bar, or 33 bar is applied horizontally (laterally) to the cross-section of the aerogel composite, the compression recovery rate may be 45% or more, 50% or more, 55% or more, 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more.

[0096] As an example, when a pressure of 3 bar or more is applied horizontally (laterally) to the cross-section of the aerogel composite, the compression recovery rate may be 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more.

[0097] As an example, when a pressure of 5 bar or more, 10 bar or more, 15 bar or more, 20 bar or more, 25 bar or more, 30 bar or more, or 35 bar or more is applied horizontally (laterally) to the cross-section of the aerogel composite, the compression recovery rate may be 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more.

[0098] As an example, when a pressure of 3 bar is applied horizontally (laterally) to the cross-section of the aerogel composite, the compression recovery rate may be 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more, preferably 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, or 92% or more, more preferably 84% or more, or 86% or more.

[0099] As an example, when a pressure of 9 bar is applied horizontally (laterally) to the cross-section of the aerogel composite, the compression recovery rates are 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, and 97% or more. It may be % or more, 98% or more, or 99% or more, preferably 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, or 92% or more, more preferably 72% or more, 74% or more, 76% or more, or 78% or more.

[0100] As an example, when a pressure of 15 bar is applied horizontally (laterally) to the cross-section of the aerogel composite, the compression recovery rates are 55% or more, 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, and 96% or more. It may be 97% or more, 98% or more, or 99% or more, preferably 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, or 92% or more, more preferably 70% or more, 72% or more, 74% or more, or 76% or more.

[0101] As an example, when a pressure of 24 bar is applied horizontally (laterally) to the cross-section of the aerogel composite, the compression recovery rates are 55% or more, 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, and 95% or more. The percentage above may be 96% or more, 97% or more, 98% or more, or 99% or more, preferably 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, or 92% or more, more preferably 70% or more, or 72% or more.

[0102] As an example, when a pressure of 30 bar is applied horizontally (laterally) to the cross-section of the aerogel composite, the compression recovery rates are 53% or more, 55% or more, 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, and 96% or more. It may be 97% or more, 98% or more, or 99% or more, preferably 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, or 92% or more, more preferably 68% or more, 70% or more, 72% or more, 74% or more, or 76% or more.

[0103] As an example, when a pressure of 33 bar is applied horizontally (laterally) to the cross-section of the aerogel composite, the compression recovery rates are 53% or more, 55% or more, 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, and 96% or more. It may be 97% or more, 98% or more, or 99% or more, preferably 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, or 92% or more, more preferably 68% or more, 70% or more, 72% or more, 74% or more, or 76% or more.

[0104] As an example, when a pressure of 37 bar is applied horizontally (laterally) to the cross-section of the aerogel composite, the compression recovery rates are 50% or more, 55% or more, 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, and 96% or more. It may be % or more, 97% or more, 98% or more, or 99% or more, preferably 55% or more, 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, or 92% or more, more preferably 55% or more, 60% or more, or 62% or more.

[0105] The thickness of the aerogel composite before compression is 20 mm or less, 15 mm or less, 14 mm or less, 13 mm or less, 12 mm or less, 11 mm or less, 10 mm or less, 9 mm or less, 8 mm or less, 7 mm or less, 6 mm or less, 5 mm or less, 4 mm or less, 3 mm or less, 2 mm or less, or 1 mm or less, and 0.5 mm or more, 1 mm or more, or 2 mm or more, and can be appropriately adjusted by adjusting the thickness of the substrate and the amount of aerogel sol impregnated into the substrate depending on the application of the aerogel composite.

[0106] With respect to the cross-section of the aerogel composite, the bar in the horizontal direction (lateral direction) is 1 bar or more, 2 bar or more, 3 bar or more, 4 bar or more, 5 bar or more, 6 bar or more, 7 bar or more, 8 bar or more, 9 bar or more, 10 bar or more, 15 bar or more, 20 bar or more, 25 bar or more, 30 bar or more, 35 bar or more, or 40 bar or more, and 50 bar or less, 45 bar or less, 40 bar or less, 35 bar or less, 35 bar or less, 30 bar or less, 20 bar or less, 15 bar or less, 10 bar or less, 9 bar or less, 8 bar or less, 7 bar or less, 6 bar or less, or 5 bar or less. When applying pressure of 4 bar or less, 3 bar or less, or 2 bar or less, the thermal transmittance after compression may be 3 times or less, 2.9 times or less, 2.8 times or less, 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less, and may be 1 time or more, or more than 1 time.

[0107] The aforementioned "thermal transmittance" refers to the rate at which heat is transferred from one layer of air to another through a solid object, and is calculated as 1 m³ per unit time. 2The thermal conductivity of an object is the value obtained by dividing the thermal conductivity of an object by its thickness. The amount of heat transferred by an object is affected by its thermal conductivity and thickness; the higher the thermal conductivity and the thinner the thickness, the greater the amount of heat transferred. Therefore, to have excellent thermal insulation performance, the thermal conductivity should be low and the thickness should be large. However, when pressure is applied to an elastic object such as an aerogel composite, the thermal conductivity and thickness may change after pressurization. In other words, unless it is a perfectly elastic material, the thickness can only decrease after pressurization, but if the thermal conductivity does not change, the decrease in thickness will increase the total amount of heat transferred. In other words, the thermal insulation performance can only decrease. Therefore, whether or not thermal insulation performance is maintained after pressurization cannot be confirmed simply by the thermal conductivity after pressurization alone, but can be confirmed by the thermal transmittance which takes into account both the thermal conductivity after pressurization and the thickness after pressurization. Even if the thermal conductivity decreases or is maintained after pressurization, if the thickness decreases significantly after pressurization, the thermal transmittance and total amount of heat transferred can only increase significantly.

[0108] The aerogel composite provided in this invention does not change significantly in either thermal conductivity or thickness even after pressurization. Therefore, the rate of increase in thermal transmittance is not high compared to before pressurization, and the thermal insulation performance can be maintained at an excellent level without a significant decrease due to pressurization.

[0109] The aforementioned "thermal transmittance after compression" refers to the ratio of thermal conductivity to the thickness of the cross-section of the aerogel composite after a predetermined time has elapsed since compressing the cross-section of the aerogel composite by applying a specific level of pressure horizontally (laterally) to the cross-section of the aerogel composite. Here, the predetermined time may be, but is not limited to, 1 second or more, 5 seconds or more, 10 seconds or more, 30 seconds or more, 1 minute or more, 5 minutes or more, 10 minutes or more, 20 minutes or more, 30 minutes or more, 40 minutes or more, 50 minutes or more, 60 minutes or more, 2 hours or more, 4 hours or more, 6 hours or more, 8 hours or more, 10 hours or more, 12 hours or more, 24 hours or more, 48 hours or more, or 96 hours or more. As an example, the thermal transmittance after compression may be measured 60 minutes (1 hour) after the aerogel composite has been compressed.

[0110] The duration for which pressure is applied to the aerogel composite is not particularly limited, but may be, for example, 1 second or more, 5 seconds or more, 10 seconds or more, 30 seconds or more, 1 minute or more, 5 minutes or more, 10 minutes or more, 20 minutes or more, 30 minutes or more, 40 minutes or more, 50 minutes or more, 1 hour or more, or 2 hours or more, and 24 hours or less, 12 hours or less, 10 hours or less, 8 hours or less, 6 hours or less, 4 hours or less, 2 hours or less, 1 hour or less, 50 minutes or less, 40 minutes or less, 30 minutes or less, 20 minutes or less, 10 minutes or less, 5 minutes or less, 1 minute or less, 30 seconds or less, or 5 seconds or less, but is not limited to these. As an example, the duration for which pressure is applied may be 10 minutes.

[0111] As an example, when a pressure of 3 bar or more, 5 bar or more, 10 bar or more, 15 bar or more, 20 bar or more, 25 bar or more, 30 bar or more, or 35 bar or more is applied horizontally (laterally) to the cross-section of the aerogel composite, the thermal transmittance after compression may be 3 times or less, 2.9 times or less, 2.8 times or less, 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less.

[0112] As an example, when a pressure of 3 bar, 9 bar, 15 bar, 24 bar, 30 bar, or 33 bar is applied horizontally (laterally) to the cross-section of the aerogel composite, the thermal transmittance after compression may be 3 times or less, 2.9 times or less, 2.8 times or less, 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less.

[0113] As an example, when pressure is applied to the cross-section of the aerogel composite at any one pressure value between 3 bar and 33 bar in the horizontal direction, the thermal transmittance after compression may be 2.0 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less compared to the thermal transmittance before compression.

[0114] As an example, when pressure is applied to the cross-section of the aerogel composite in the horizontal direction (lateral direction) at any pressure value between 3 bar and 24 bar, the thermal transmittance after compression may be 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less compared to the thermal transmittance before compression.

[0115] As an example, when pressure is applied to the cross-section of the aerogel composite at any one pressure value between 3 bar and 9 bar in the horizontal direction, the thermal transmittance after compression may be 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.45 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less compared to the thermal transmittance before compression.

[0116] As an example, when pressure is applied to the cross-section of the aerogel composite at any one pressure value between 9 bar and 33 bar in the horizontal direction, the thermal transmittance after compression may be 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less compared to the thermal transmittance before compression.

[0117] As an example, when pressure is applied to the cross-section of the aerogel composite at any one pressure value between 9 bar and 24 bar in the horizontal direction, the thermal transmittance after compression may be 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less compared to the thermal transmittance before compression.

[0118] As an example, when pressure is applied to the cross-section of the aerogel composite at any one pressure value between 15 bar and 33 bar in the horizontal direction, the thermal transmittance after compression may be 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, or 1.05 times or less compared to the thermal transmittance before compression.

[0119] As an example, when pressure is applied to the cross-section of the aerogel composite at any one pressure value between 15 bar and 30 bar in the horizontal direction, the thermal transmittance after compression may be 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, or 1.05 times or less compared to the thermal transmittance before compression.

[0120] As an example, when pressure is applied to the cross-section of the aerogel composite at any one of the pressure values ​​from 24 bar to 33 bar in the horizontal direction, the thermal transmittance after compression may be 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less compared to the thermal transmittance before compression.

[0121] As an example, when pressure is applied to the cross-section of the aerogel composite at any one pressure value between 24 bar and 30 bar in the horizontal direction, the thermal transmittance after compression may be 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less compared to the thermal transmittance before compression.

[0122] As an example, when pressure is applied to the cross-section of the aerogel composite at any one pressure value between 30 bar and 33 bar in the horizontal direction, the thermal transmittance after compression may be 3 times or less, 2.9 times or less, 2.8 times or less, 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less compared to the thermal transmittance before compression.

[0123] As an example, when pressure is applied to the cross-section of the aerogel composite with a pressure value of 3 bar in the horizontal direction, the thermal transmittance after compression may be 1.8 times or less, 1.24 times or less, 1.2 times or less, 1.15 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less compared to the thermal transmittance before compression, and preferably 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less.

[0124] As an example, when a pressure of 9 bar is applied horizontally (laterally) to the cross-section of the aerogel composite, the thermal transmittance after compression may be 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less compared to the thermal transmittance before compression, and preferably 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less.

[0125] As an example, when a pressure of 15 bar is applied horizontally (laterally) to the cross-section of the aerogel composite, the thermal transmittance after compression is 2.35 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1 It may be 0.03 times or less, 1.02 times or less, or 1.01 times or less, preferably 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, or 1.05 times or less, more preferably 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less.

[0126] As an example, when a pressure of 24 bar is applied horizontally (laterally) to the cross-section of the aerogel composite, the thermal transmittance after compression is 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, and 1.05 times or less compared to the thermal transmittance before compression. It may be 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less, preferably 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, or 1.05 times or less, more preferably 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less.

[0127] As an example, when a pressure of 30 bar is applied horizontally (laterally) to the cross-section of the aerogel composite, the thermal transmittance after compression is 3 times or less, 2.9 times or less, 2.8 times or less, 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less. It may be 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less, preferably 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, or 1.05 times or less, more preferably 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less.

[0128] As an example, when a pressure of 33 bar is applied horizontally (laterally) to the cross-section of the aerogel composite, the thermal transmittance after compression is 3 times or less, 2.9 times or less, 2.8 times or less, 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1. It may be 0.4 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less, preferably 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less, more preferably 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, or 1.2 times or less.

[0129] As an example, when pressures of 3 bar, 9 bar, and 24 bar are applied horizontally (laterally) to the cross-section of the aerogel composite, the thermal transmittance after compression may be 1.8 times or less, or 1.7 times or less, compared to the thermal transmittance before compression, preferably more than 1 time, 1.8 times or less, or more than 1 time and 1.7 times or less. As an example, the thermal transmittance after compression may be 1.8 times or less compared to the thermal transmittance before compression. As an example, the thermal transmittance after compression may be more than 1 time and 1.8 times or less compared to the thermal transmittance before compression.

[0130] The aerogel composite provided in this invention maintains its thermal transmittance within a specific range before and after compression, regardless of the pressure (or compression) applied, thereby maintaining an excellent level of thermal insulation performance without a significant decrease in thermal insulation performance.

[0131] In more detail, the thermal transmittance obtained after compressing the aerogel composite of the present invention at at least one pressure value between 0 and 24 bar satisfies the following equation 4: [Formula 4] {(Thermal transmittance before and after compression (a)) - (Average thermal transmittance before and after compression (b))} = (Average thermal transmittance before and after compression (b)) × A

[0132] In Equation 4, "thermal transmittance before and after compression (a)" means the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with respect to its cross-section at at least one pressure value in the range of 0 to 24 bar. For example, it may mean the thermal transmittance obtained after applying pressures of 0 bar, 3 bar, 9 bar, or 24 bar to the aerogel composite. Here, a pressure of 0 bar means no pressurization (uncompressible), and therefore the thermal transmittance obtained after compressing with a pressure of 0 bar means the thermal transmittance of an unpressurized aerogel composite.

[0133] Furthermore, the "average value of thermal transmittance before and after compression (b)" refers to the thermal transmittance of an aerogel composite that has not been pressurized (or compressed) and the average value of the thermal transmittance obtained after compressing the aerogel composite with at least two pressure values ​​within the range of 0 bar to 24 bar in the horizontal direction (lateral direction) relative to the cross-section of the aerogel composite. As an example, it may refer to the thermal transmittance of an unpressurized (uncompressed) aerogel composite and the average value of the thermal transmittance obtained after compressing the aerogel composite by applying pressure at at least two pressure values ​​from 3 bar, 9 bar, and 24 bar.

[0134] The aforementioned A is a real number between -0.40 and +0.40, a real number between -0.35 and +0.35, a real number between -0.34 and +0.34, a real number between -0.33 and +0.33, a real number between -0.32 and +0.32, a real number between -0.31 and +0.31, a real number between -0.30 and +0.30, a real number between -0.25 and +0.25, a real number between -0.24 and +0.24, and a real number between -0.23 and +0. It can be a real number of 23, a real number between -0.22 and +0.22, a real number between -0.21 and +0.21, a real number between -0.20 and +0.20, a real number between -0.19 and +0.19, a real number between -0.15 and +0.15, a real number between -0.14 and +0.14, a real number between -0.13 and +0.13, a real number between -0.12 and +0.12, or a real number between -0.11 and +0.11.

[0135] As an example, the thermal transmittance of an uncompressed (0 bar compression) aerogel composite may satisfy equation 4 above. In this case, the average value of the thermal transmittance before and after compression (b) may represent the thermal transmittance of the uncompressed aerogel composite and the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with respect to its cross-section at a pressure of at least two of the following values: 3 bar, 9 bar, and 24 bar.

[0136] As an example, the thermal transmittance obtained after compressing the aerogel composite with a pressure of 3 bar, 9 bar, or 24 bar may satisfy equation 4. In this case, the average value of the thermal transmittance before and after compression (b) may represent the thermal transmittance of the uncompressed (0 bar compressed) aerogel composite and the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with respect to its cross-section with at least two of the pressure values ​​of 3 bar, 9 bar, and 24 bar.

[0137] As an example, the thermal transmittance of an uncompressed (0 bar compressed) aerogel composite may satisfy equation 4 above. In this case, the average value of the thermal transmittance before and after compression (b) may represent the thermal transmittance of the uncompressed aerogel composite and the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) at pressure values ​​of 3 bar, 9 bar, and 24 bar, respectively, with respect to the cross-section.

[0138] As an example, the thermal transmittance obtained after compressing the aerogel composite with a pressure of 3 bar, 9 bar, or 24 bar may satisfy Equation 4. In this case, the "average value of thermal transmittance before and after compression (b)" may mean the thermal transmittance of the uncompressed (0 bar compressed) aerogel composite and the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with respect to its cross-section at pressures of 3 bar, 9 bar, and 24 bar, respectively.

[0139] As an example, the thermal transmittance of an uncompressed (0 bar compression) aerogel composite may satisfy equation 4 above. In this case, the average value of the thermal transmittance before and after compression (b) may represent the thermal transmittance of the uncompressed aerogel composite and the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with pressure values ​​of 3 bar and 9 bar, respectively.

[0140] As an example, the thermal transmittance obtained after compressing the aerogel composite with a pressure of 3 bar or 9 bar may satisfy equation 4. In this case, the average value of the thermal transmittance before and after compression (b) may represent the thermal transmittance of the uncompressed (0 bar compressed) aerogel composite and the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with pressure values ​​of 3 bar and 9 bar, respectively, with respect to the cross-section.

[0141] As an example, the above-mentioned "average value of thermal transmittance before and after compression (b)" means the average value of the thermal transmittance of the uncompressed (0 bar compression) aerogel composite and the thermal transmittance obtained after compressing the aerogel composite by applying pressures of 3 bar, 9 bar, and 24 bar horizontally (laterally) to the cross-section of the aerogel composite, in which case A may be a real number between -0.40 and +0.40, a real number between -0.35 and +0.35, a real number between -0.30 and +0.30, or a real number between -0.25 and +0.25."

[0142] As an example, the average value of the thermal transmittance before and after compression (b) refers to the average value of the thermal transmittance of the uncompressed (0 bar compressed) aerogel composite and the thermal transmittance obtained after compressing the aerogel composite by applying pressures of 3 bar and 9 bar in the horizontal direction (lateral direction) to the cross-section of the aerogel composite. In this case, A can be a real number between -0.23 and +0.23, a real number between -0.22 and +0.22, a real number between -0.21 and +0.21, or a real number between -0.20 and +0.20.

[0143] As an example, the thermal transmittance obtained after compressing the aerogel composite at a pressure of 0 bar, 3 bar, 9 bar, or 24 bar may satisfy Equation 4. In this case, the "average value of thermal transmittance before and after compression (b)" may mean the thermal transmittance of the uncompressed (0 bar compressed) aerogel composite and the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) at pressures of 3 bar, 9 bar, and 24 bar, respectively, with respect to the cross-section. Here, A may be a real number between -0.40 and +0.40.

[0144] As an example, the thermal transmittance obtained after compressing the aerogel composite at a pressure of 3 bar, 9 bar, or 24 bar may satisfy Equation 4. In this case, the average value of the thermal transmittance before and after compression (b) may mean the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) at pressure values ​​of 3 bar, 9 bar, and 24 bar, respectively, with respect to the cross-section. Here, A may be a real number between -0.23 and +0.23.

[0145] The average value of the thermal transmittance before and after compression (b) refers to the average value of the thermal transmittance of the uncompressed (0 bar compressed) aerogel composite and the thermal transmittance obtained after compressing the aerogel composite by applying pressures of 3 bar and 9 bar in the horizontal direction (lateral direction) to the cross-section of the aerogel composite, in which case A can be a real number between -0.23 and +0.23, a real number between -0.22 and +0.22, a real number between -0.21 and +0.21, or a real number between -0.20 and +0.20.

[0146] Furthermore, the aerogel composite provided in this invention maintains its thermal transmittance within a specific range even when pressurized (or compressed) under any pressure, thereby maintaining an excellent level of thermal insulation performance without a significant decrease.

[0147] In more detail, the thermal transmittance obtained after compressing the aerogel composite of the present invention at at least one pressure value between 3 and 30 bar satisfies the following equation 5: [Formula 5] {(Compressed heat transfer coefficient (c) - Average heat transfer coefficient after compression (d))} = (Average heat transfer coefficient after compression (d)) × B

[0148] In equation 5, "thermal transmittance before and after compression (c)" means the thermal transmittance obtained after compressing the aerogel composite with at least one pressure value in the range of 3 to 30 bar in the horizontal direction (lateral direction) with respect to the cross-section of the aerogel composite. For example, it may mean the thermal transmittance obtained after applying pressures of 3 bar, 9 bar, 15 bar, 24 bar, or 30 bar, and for other examples, it may mean the thermal transmittance obtained after applying pressures of 3 bar, 9 bar, or 24 bar.

[0149] Furthermore, the "average value of thermal transmittance after compression (d)" refers to the average value of thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with respect to its cross-section at at least two pressure values ​​within the range of 3 bar to 30 bar. As an example, it may refer to the average value of thermal transmittance obtained after compressing with pressures of 3 bar, 9 bar, and 24 bar, respectively.

[0150] The aforementioned B is a real number between -0.30 and +0.30, a real number between -0.29 and +0.29, a real number between -0.28 and +0.28, a real number between -0.27 and +0.27, a real number between -0.26 and +0.26, a real number between -0.25 and +0.25, a real number between -0.24 and +0.24, a real number between -0.23 and +0.23, a real number between -0.22 and +0.22, and -0 It can be a real number between 0.21 and +0.21, a real number between -0.20 and +0.20, a real number between -0.19 and +0.19, a real number between -0.15 and +0.15, a real number between -0.14 and +0.14, a real number between -0.13 and +0.13, a real number between -0.12 and +0.12, a real number between -0.11 and +0.11, or a real number between -0.10 and +0.10.

[0151] As an example, the thermal transmittance obtained after compressing the aerogel composite with a pressure of 3 bar, 9 bar, or 24 bar may satisfy equation 5. In this case, in equation 5, the thermal transmittance after compression (c) means the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with a pressure of 3 bar, 9 bar, or 24 bar relative to the cross-section, and the average value of the thermal transmittance after compression (d) may mean the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with at least two pressure values ​​from 3 bar, 9 bar, and 24 bar relative to the cross-section.

[0152] As an example, the thermal transmittance obtained after compressing the aerogel composite at a pressure of 3 bar, 9 bar, or 24 bar may satisfy equation 5. In this case, in equation 5, the thermal transmittance after compression (c) means the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with a pressure of 3 bar, 9 bar, or 24 bar relative to the cross-section, the average value of the thermal transmittance after compression (d) means the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with a pressure of 3 bar, 9 bar, and 24 bar, respectively, and B can be a real number between -0.30 and +0.30, a real number between -0.29 and +0.29, a real number between -0.28 and +0.28, a real number between -0.27 and +0.27, a real number between -0.26 and +0.26, a real number between -0.25 and +0.25, a real number between -0.24 and +0.24, or a real number between -0.23 and +0.23.

[0153] As an example, the thermal transmittance obtained after compressing the aerogel composite at pressures of 3 bar, 9 bar, and 24 bar may satisfy equation 5. In this case, in equation 5, the thermal transmittance after compression (c) means the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with respect to its cross-section at one of the pressure values ​​of 3 bar, 9 bar, and 24 bar, the average value of the thermal transmittance after compression (d) means the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with respect to its cross-section at the respective pressure values ​​of 3 bar, 9 bar, and 24 bar, and B can be a real number between -0.30 and +0.30, a real number between -0.29 and +0.29, a real number between -0.28 and +0.28, a real number between -0.27 and +0.27, a real number between -0.26 and +0.26, a real number between -0.25 and +0.25, a real number between -0.24 and +0.24, or a real number between -0.23 and +0.23.

[0154] Furthermore, for the aerogel composite, the rate of change (C) of the thermal transmittance after compression per unit applied pressure, as expressed in the following formula 6, is -0.15 or higher, -0.14 or higher, -0.13 or higher, -0.12 or higher, -0.11 or higher, -0.10 or higher, -0.09 or higher, -0.08 or higher, -0.07 or higher, -0.06 or higher, -0.05 or higher, -0.04 or higher, -0.03 or higher, -0 It can be a real number greater than or equal to 0.02, or greater than or equal to -0.01, and can be a real number less than or equal to +0.15, less than or equal to +0.14, less than or equal to +0.13, less than or equal to +0.12, less than or equal to +0.11, less than or equal to +0.10, less than or equal to +0.09, less than or equal to +0.08, less than or equal to +0.07, less than or equal to +0.06, less than or equal to +0.05, less than or equal to +0.04, less than or equal to +0.03, less than or equal to +0.02, or less than or equal to +0.01. Preferably, it can be a real number between -0.15 and +0.15, between -0.14 and +0.14, between -0.13 and +0.13, between -0.12 and +0.12, between -0.11 and +0.11, or between -0.10 and +0.10. [Formula 6] C = {(thermal transmittance after compression at pressure x - thermal transmittance after compression at pressure y)} / (xy)

[0155] In equation 6, x and y are each independent pressure values ​​(in bar) within the pressure range of 3 to 24 bar, and are different pressure values ​​from each other.

[0156] As an example, in equation 6, x and y can each independently be any one of the pressure values ​​of 3 bar, 9 bar, 15 bar, and 24 bar.

[0157] As an example, in equation 6 above, x could be 24 bar and y could be 3 bar.

[0158] As an example, in equation 6 above, x could be 24 bar and y could be 9 bar.

[0159] As an example, in equation 6 above, x could be 15 bar and y could be 9 bar.

[0160] As an example, in equation 6 above, x may be 24 bar and y may be 15 bar.

[0161] As described above, when measuring the recovery rate and heat reflux rate of an aerogel composite after compression using a press or the like, it is possible to prepare a single specimen from the aerogel composite and perform the measurements. However, if the width or length of the aerogel composite is smaller than the pressure-applying part of the measuring equipment, the measurement results can be considered substantially the same as those obtained from a single specimen even if the aerogel composite is cut into two or more pieces and rearranged so that both the width and length are larger than the pressure-applying equipment before measuring the compression recovery rate and heat reflux rate.

[0162] As an example, the recovery rate after compression or the thermal transmittance after compression may be measured on a rectangular aerogel composite specimen having dimensions of 30 cm × 24 cm. In this case, if the width or length of the fabricated aerogel composite is less than 30 cm or 24 cm, two or more specimens may be placed side by side, rearranged so that the size of each specimen is 30 cm × 24 cm, and then measured on such paper pieces.

[0163] The aerogel composite may have a compressive strength at 10% deformation of 20kPa to 80kPa, 20kPa to 70kPa, 30kPa to 80kPa, 30kPa to 70kPa, 35kPa to 80kPa, or 35kPa to 70kPa, and may exhibit excellent mechanical strength. Here, the compressive strength may be measured by manufacturing a specimen in accordance with the ASTM C165 standard.

[0164] The aerogel composite has a tensile strength of 30 N / cm². 2 ~60N / cm 2 , 40 N / cm 2 ~55N / cm 2 , or 45 N / cm 2 ~55N / cm 2 It may be a material that is highly flexible. Here, the tensile strength may be measured by manufacturing a specimen in accordance with the ASTM D638 standard.

[0165] The aerogel composite can generally be formed by the steps of producing a silica sol, impregnating a fibrous substrate with the silica sol and then gelling it, and drying it. Each step is described below. However, the specific manufacturing processes and examples thereof described herein are not intended to be limited to any particular type of aerogel or method for producing the same. This specification may include any aerogel formed by any relevant manufacturing method known to the ordinary art.

[0166] Steps for producing silica sol In the present invention, a silica sol can be produced by mixing a silica precursor composition and a catalyst composition.

[0167] The silica precursor composition may contain water and / or a polar organic solvent in addition to the silica precursor.

[0168] The silica precursor can be any precursor usable to form a silica aerogel, but may be, for example, a silicon-containing alkoxide compound. More specifically, these may be tetraalkyl silicates such as tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetra-sec-butyl orthosilicate, tetra-tert-butyl orthosilicate, tetrahexyl orthosilicate, tetracyclohexyl orthosilicate, and tetradodecyl orthosilicate. More specifically, in the present invention, the silica precursor may be tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), or a mixture thereof.

[0169] Furthermore, the silica precursor may be a water glass solution. Here, the water glass solution may refer to a diluted solution obtained by adding distilled water to water glass and mixing it, and the water glass may be sodium silicate (Na2SiO3), which is an alkali silicate salt obtained by dissolving silicon dioxide (SiO2) and alkali.

[0170] Furthermore, the silica precursor may contain pre-hydrolyzed TEOS (HTEOS). HTEOS is an ethyl silicate oligomer with a broad molecular weight distribution, and its properties, such as gelation time, can be adjusted when synthesizing it from TEOS monomers into an oligomer, making it easily applicable to the user's reaction conditions. It also has the advantage of producing reproducible properties for the final product. HTEOS can generally be synthesized by a condensation reaction of TEOS that undergoes a partial hydration step under acidic conditions. In other words, HTEOS is an oligomer produced by condensing TEOS, and the oligomer may be partially hydrated.

[0171] The silica precursor composition may further contain a silicate containing a hydrophobic group. The silicate containing the hydrophobic group is not limited in type as long as it is an alkylsilane compound containing an alkyl group that induces hydrophobicity and a silane active group that can react with the -Si-O- active group of the wet gel. Specific examples include, but are not limited to, one or more selected from the group consisting of methyltriethoxysilane (MTES), trimethylethoxysilane (TMES), trimethylsilanol (TMS), methyltrimethoxysilane (MTMS), dimethyldiethoxysilane (DMDEOS), ethyltriethoxysilane (ETES), and phenyltriethoxysilane (PTES).

[0172] If the silica precursor contains a silicate containing the hydrophobic group in the composition, it may be included with the tetraalkyl silicate in a molar ratio of 2:98 to 98:2 (molar ratio of silicate containing the hydrophobic group to tetraalkyl silicate). Within this range, it is possible to ensure the strength and thermal insulation performance of the aerogel with high efficiency while preventing shrinkage during drying at atmospheric pressure and thus preventing a decrease in thermal insulation performance.

[0173] The silica concentration of the silica precursor composition is 10 kg / m³. 3 ~100kg / m 3 , 20kg / m 3 ~80kg / m 3 , 30 kg / m3 ~70kg / m 3 , 30 kg / m 3 ~60kg / m 3 , or 35 kg / m 3 ~45kg / m 3 This is possible, but not limited to. The concentration of silica is the concentration of silica contained in the silica precursor relative to the silica precursor composition, and can be appropriately adjusted by varying the content of the silica precursor, organic solvent, and water.

[0174] The silica precursor may be used in an amount such that the silica content in the silica sol is 0.1% to 30% by weight, but is not limited to this. A silica content that satisfies the above range is preferable in that it ensures excellent mechanical properties of the aerogel composite, particularly flexibility, while also providing improved thermal insulation.

[0175] The aforementioned organic solvent may include alcohols, specifically monohydric alcohols such as methanol, ethanol, isopropanol, and butanol; polyhydric alcohols such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, and sorbitol; or combinations thereof; however, other solvents known to the ordinary art in this field may also be used without limitation. In the present invention, the polar organic solvent may be a monohydric alcohol having 1 to 6 carbon atoms, such as methanol, ethanol, isopropanol, and butanol, considering its miscibility with water and aerogel, for example, ethanol.

[0176] The aforementioned polar organic solvent promotes the surface modification reaction and can be used in appropriate amounts by a typical technician, taking into account the degree of hydrophobicity of the final aerogel composite.

[0177] In producing the silica precursor described above, the silica precursor and the organic solvent can be mixed in a weight ratio of 1:0.1 to 1.5, 1:0.5 to 1.5, or 1:0.5 to 1.2, but are not limited to this.

[0178] Furthermore, in order to produce the silica precursor that has undergone electrolysis, the silica precursor and water may be mixed in a molar ratio of 1:0.5 to 10.1:1 to 8, or 1:3 to 6, but this is not limited to such a method.

[0179] Furthermore, when the silica precursor is produced, if the silica precursor includes a pre-hydrolyzed silica precursor (e.g., pre-hydrolyzed TEOS), the silica concentration may be satisfied by mixing the pre-hydrolyzed silica precursor (e.g., pre-hydrolyzed TEOS) and an organic solvent in a weight ratio of 1:2 to 10, 1:3 to 8, or 1:3 to 6, but this is not limited to such mixing.

[0180] The silica precursor composition may further contain an acid catalyst, more specifically, when an alkoxysilane compound is used as the precursor instead of a hydrolysate, the acid catalyst may further be included. In this case, any acid catalyst that has a pH of 3 or less, especially one that makes the pH approximately 3, can be used without restriction, but examples include hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, oxalic acid, or acetic acid. In this case, the amount of acid catalyst added may be such that the pH of the sol becomes 3 or less, and it may be added in the form of an aqueous solution dissolved in water.

[0181] The catalyst composition may contain an inorganic base such as sodium hydroxide or potassium hydroxide as a base catalyst; or an organic base such as ammonium hydroxide. Specific examples include, but are not limited to, sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), ammonia (NH3), ammonium hydroxide (NA4OH; aqueous ammonia), tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), methylamine, ethylamine, isopropylamine, monoisopropylamine, diethylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, choline, monoethanolamine, diethanolamine, 2-aminoethanol, 2-(ethylamino)ethanol, 2-(methylamino)ethanol, N-methyldiethanolamine, dimethylaminoethanol, diethylaminoethanol, nitrilotriethanol, 2-(2-aminoethoxy)ethanol, 1-amino-2-propanol, triethanolamine, monopropanolamine, dibutanolamine, pyridine, or combinations thereof.

[0182] The base catalyst may be included in an amount such that the pH of the sol is between 5 and 9. If the pH of the sol deviates from this range, gelation may not be easy, or the gelation rate may become excessively slow, potentially reducing process efficiency. Furthermore, since the base may precipitate if added in solid form, it may be preferable to add it in a diluted solution with an aqueous solvent or the aforementioned organic solvent. In this case, the dilution ratio of the base catalyst and the organic solvent, specifically the alcohol, may be 1:4 to 1:100 based on volume, but is not limited to this.

[0183] The catalyst composition further contains an alkoxysilane compound having a hydrophobic group, which allows such a hydrophobic agent to react with the silica-wet gel to strengthen the structure and perform surface modification.

[0184] The alkoxysilane compound having a hydrophobic group is not limited to any alkylsilane compound containing an alkyl group that induces hydrophobicity and a silane active group that can react with the -Si-O- active group of the wet gel. Specific examples include, but are not limited to, one or more selected from the group consisting of trimethylethoxysilane (TMES), trimethylsilanol (TMS), trimethylchlorosilane (TMCS), methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), dimethyldiethoxysilane (DMDEOS), ethyltriethoxysilane, and phenyltriethoxysilane.

[0185] The alkoxysilane compound having a hydrophobic group may be included in an amount of 3 to 15 parts by weight, 5 to 10 parts by weight, or 6 to 8 parts by weight based on 100 parts by weight of silica sol, but is not limited to these amounts.

[0186] However, if the catalyst composition contains an alkoxysilane compound having a hydrophobic group, it may contain water to promote the surface modification reaction. The catalyst composition may contain 3 to 8 equivalents, 4 to 8 equivalents, or 5 to 6 equivalents of water based on 1 equivalent of the hydrophobic agent.

[0187] To produce the silica sol, the silica precursor composition and the catalyst composition may be mixed in a volume ratio of 1:0.01 to 10.0, 1:0.01 to 5.0, or 1:0.01 to 2.0, but are not limited to these.

[0188] In the present invention, additives may be further added to the silica sol as needed. In this case, any known additives that can be added when manufacturing aerogels may be used, but for example, opacifying agents and flame retardants may be used as additives.

[0189] The aforementioned additive may be added in amounts of 0.1% to 10% by weight, 0.1% to 7% by weight, 0.5% to 7% by weight, or 0.5% to 5% by weight relative to the silica content of the aerogel, but is not limited to these amounts.

[0190] Step to gel silica sol In this invention, after impregnating a substrate with silica sol, the silica sol can be gelled.

[0191] The impregnation step is a step to allow the catalytic silica sol to penetrate into the internal voids of the substrate. This step can be carried out by introducing the catalytic silica sol and the substrate into a reaction vessel, or by spraying the catalytic silica sol onto the substrate as it moves on a conveyor belt in a roll-to-roll process. In this case, the substrate may be lightly pressed to ensure sufficient impregnation in order to improve the bonding between the substrate and the silica sol. Next, the material may be pressurized to a constant thickness at a constant pressure to remove excess silica sol and reduce the drying time.

[0192] The temperature of the silica sol in the reaction vessel may be 1 to 40°C, 20 to 40°C, 25 to 40°C, 30 to 40°C, or 35 to 45°C. It is preferable that the temperature of the silica sol in the reaction vessel satisfies the above range, as this makes it easier to achieve the viscosity range of the catalyzed sol as described above, and allows the desired level of viscosity to be satisfied even with a relatively short residence time.

[0193] The catalystd silica sol can be impregnated into the substrate in a volume ratio of 0.1 to 10:1 (catalyzed silica sol:substrate), 0.1 to 1:1, 0.3 to 1:1, 0.5 to 1:1, or 0.6 to 1:1, but is not limited to these.

[0194] Simultaneously with or sequentially after the silica sol impregnation step, the silica sol impregnated into the substrate can be gelled.

[0195] In this invention, a substrate impregnated with a catalytic sol can be gelled on a moving element such as a conveyor belt.

[0196] The aforementioned "gelation" may refer to a sol-gel reaction, and the aforementioned "sol-gel reaction" may refer to the formation of a network structure from a silicon-unit precursor material. Here, the network structure may refer to a planar network pattern structure in which a specific polygon consisting of one or more types of atomic arrangements is connected, or a structure in which a three-dimensional skeletal structure is formed by sharing vertices, corners, faces, etc., of a specific polyhedron.

[0197] The gelation can be carried out under ambient temperatures of 20 to 40°C, 20 to 30°C, 25 to 40°C, 30 to 40°C, or 35 to 40°C, and preferably under ambient temperatures of 30 to 40°C or 35 to 40°C, which can strengthen the processed structure.

[0198] Furthermore, the gelation time may be 1 to 120 minutes, 1 to 100 minutes, 1 to 60 minutes, 5 to 60 minutes, 5 to 40 minutes, 10 to 40 minutes, 10 to 30 minutes, or 10 to 20 minutes, but is not limited to these.

[0199] Step to mature the gelled wet gel complex. The present invention may further include, if necessary, a maturation step in which the wet gel composite obtained from gelation as described above is left at an appropriate temperature to allow the chemical changes to take place completely. In the maturation step, the network structure formed by gelation can be made even more robust, and the mechanical stability of the aerogel composite can be improved.

[0200] The maturation step can be carried out by leaving the gelled wet gel complex at an appropriate temperature, or by adding a cross-linking-promoting compound.

[0201] Furthermore, during the maturation step, a solution of a base catalyst such as sodium hydroxide (NaOH), potassium hydroxide (KOH), ammonium hydroxide (NH4OH), triethylamine, or pyridine, diluted in an organic solvent to a concentration of 1 to 10%, may be added in the presence of the wet gel complex. In this case, the Si-O-Si bond is maximally induced within the aerogel, further strengthening the network structure of the silica gel and making it easier to maintain the porosity structure in the subsequent drying step. The organic solvent may be the alcohols mentioned above, but more specifically, it may include ethanol.

[0202] The aforementioned maturation step may be carried out by leaving the product at a temperature of 30°C to 80°C, 40°C to 80°C, or 50°C to 80°C for 0.1 to 20 hours, 0.5 to 15 hours, 0.5 to 10 hours, 0.5 to 7 hours, or 1 to 5 hours to strengthen the porosity structure. Within this range, it is possible to prevent a decrease in productivity while preventing solvent loss due to evaporation and thus preventing an increase in production costs.

[0203] Furthermore, the aging step may involve primary aging at 30°C to 80°C for 0.1 to 5 hours to strengthen the pore structure, followed by secondary aging at 30°C to 80°C for 0.1 to 20 hours, 0.5 to 15 hours, 0.5 to 10 hours, 0.5 to 7 hours, or 1 to 5 hours in the presence of a solution of the catalyst diluted to 1 to 10% in an organic solvent.

[0204] Furthermore, during the aging step (or during the secondary aging if the process is carried out in two stages), a mixed solution of an alkoxysilane compound and an alcohol can be added to provide not only an unreacted sol but also an additional sol precursor source, thereby inducing additional gelation of the silica gel network structure and further strengthening the gel structure. In this case, the alkoxysilane compound may be present in an amount of 0.5 to 9.5 parts by weight, 1.0 to 9.5 parts by weight, or 1.5 to 9.5 parts by weight per 100 parts by weight of the total aging solution.

[0205] The aforementioned alkoxysilane compounds include tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetra-sec-butyl orthosilicate, tetra-tert-butyl orthosilicate, tetrahexyl orthosilicate, tetracyclohexyl orthosilicate, and tetradodecyl orthosilicate. It may contain one or more substances selected from the group consisting of orthosilicate, methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), trimethylethoxysilane (TMES), trimethylsilanol (TMS), trimethylchlorosilane (TMCS), ethyltriethoxysilane (ETES), dimethyldiethoxysilane (DMDEOS), and phenyltriethoxysilane.

[0206] Furthermore, the alcohol may be, in more detail, a monohydric alcohol such as methanol, ethanol, isopropanol, or butanol; or a polyhydric alcohol such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, or sorbitol, preferably a monohydric alcohol having 1 to 6 carbon atoms such as methanol, ethanol, isopropanol, or butanol, for example, ethanol, but not limited to these.

[0207] The maturation step may be carried out in a separate reaction vessel after the gelled wet gel composite has been collected, or it may be carried out inside the reaction vessel in which the gelling step was performed.

[0208] Steps to modify the surface of the matured wet gel composite. The present invention may further include a surface modification step in which the surface of the wet gel composite obtained by gelation as described above or the surface of the matured wet gel composite is made hydrophobic in the presence of a surface modifier, if necessary.

[0209] The surface modifier can be any compound that hydrophobizes the surface of the wet gel, but may include, for example, silane compounds, siloxane compounds, silanol compounds, silazane compounds, or combinations thereof. Specific examples include, for example, trimethylchlorosilane (TMCS), dimethyldimethoxysilane, dimethyldiethoxysilane, methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), trimethylethoxysilane (TMES), vinyltrimethoxysilane, ethyltriethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane, and Silane compounds including traethoxysilane, dimethyldichlorosilane, and 3-aminopropyltriethoxysilane; siloxane compounds including polydimethylsiloxane, polydiethylsiloxane, or octamethylcyclotetrasiloxane; silanol compounds including trimethylsilanol, triethylsilanol, triphenylsilanol, and t-butyldimethylsilanol; 1,2-diethyldisilazane, 1,1,2,2-tetramethyldisilazane, and 1,1,3,3-tetramethyldisilazane Silazane compounds including disilazane, 1,1,1,2,2,2-hexamethyldisilazane (HMDS), 1,1,2,2-tetraethyldisilazane, or 1,2-diisopropyldisilazane; or combinations thereof; however, these may be and may not be limited to these.

[0210] The surface modifier can be used in solution form diluted in an organic solvent. Here, the organic solvent may be an alcohol (organic solvent), in which case the surface modifier can be diluted to 1 to 15% by volume based on the volume of the total diluted solution.

[0211] Furthermore, the surface modifier may be added in an amount of 0.01 to 90% by volume relative to the wet gel composite in order to achieve a sufficient surface modification effect, but is not limited to this amount.

[0212] The surface modification step may be carried out at a temperature of 50 to 90°C or 50 to 80°C for 1 to 24 hours, but is not limited to this.

[0213] Drying step The present invention may include a drying step of drying the surface-modified wet gel composite to obtain an aerogel composite.

[0214] The aforementioned drying process removes only the solvent while maintaining the porous structure of the matured gel, and can be carried out by methods such as supercritical drying or atmospheric pressure drying.

[0215] The supercritical drying process is carried out using supercritical carbon dioxide. For example, after placing a matured wet gel composite into a supercritical drying reactor, a solvent replacement process is performed in which liquid CO2 is packed in to replace the alcohol solvent inside the wet gel with CO2. Then, the temperature is raised to 40 to 70°C at a constant heating rate, for example, 0.1°C / min to 1°C / min. After that, a pressure above the pressure at which carbon dioxide becomes supercritical, for example, 100 bar to 150 bar, is maintained, and the carbon dioxide can be maintained in a supercritical state for a certain period of time, specifically 20 minutes to 1 hour. Generally, carbon dioxide becomes supercritical at a temperature of 31°C and a pressure of 73.8 bar. After maintaining the constant temperature and pressure at which carbon dioxide becomes supercritical for 2 to 12 hours, more specifically 2 to 6 hours, the pressure can be gradually removed to complete the supercritical drying process and produce an aerogel composite, but this is not limited to this.

[0216] Furthermore, the atmospheric pressure drying process may be carried out by conventional methods such as hot air drying or IR drying at a temperature of 70 to 200°C and atmospheric pressure (1 ± 0.3 atm), but is not limited to these methods.

[0217] In addition to the steps described above, the present invention also includes the acidification of a basic metal oxide precursor (e.g., sodium silicate) in water for the production of a hydrogel. Salt byproducts can be removed from the silicate precursor by ion exchange and / or by subsequent washing of the formed gel with water. Removal of water from the pores of the gel can be carried out by exchange with a polar organic solvent, such as ethanol, methanol, or acetone. The liquid in the gel is then at least partially extracted using innovative processing and extraction techniques.

[0218] In addition to the steps described above, the present invention also includes reducing damaging capillary forces at the solvent / pore interface by chemical deformation of the matrix material in a wet gel state through conversion of surface hydroxyl groups of hydrophobic trimethylsilyl ether, thereby enabling liquid pivoting from the gel material at temperatures and pressures below the critical point of the solvent.

[0219] In addition to the steps described above, the present invention may also involve freezing the liquid (solvent) within the gel material at a lower temperature, followed by a sublimation step to remove the solvent from the gel material. Such removal or drying of the solvent from the gel material is understood to be within the scope of this disclosure. Such removal largely preserves the structure of the gel and produces an aerogel with unique properties.

[0220] The aerogel composite provided in this invention can be usefully used as an insulating material, heat-insulating material, or non-combustible material in various industrial equipment such as piping and industrial furnaces, as well as in plant facilities for heating and cooling, and in aircraft, ships, automobiles, electronic equipment, batteries, and more.

[0221] Another embodiment of the present invention relates to a thermal insulation member comprising an aerogel composite provided in the present invention.

[0222] The thermal insulation member may include the aerogel composite described above and a support member located on at least one of the upper and lower surfaces of the aerogel composite.

[0223] Examples of the support members include film-like support members, sheet-like support members, foil-like support members, and porous support members.

[0224] The aforementioned film-like support member is made by forming a polymer raw material into a thin film, and examples include organic films such as PET and polyimide, and glass films (including metal-deposited films).

[0225] The aforementioned sheet-like support member is made by molding organic, inorganic, or metallic fibrous raw materials, and examples include paper, nonwoven fabric (including glass mat), organic fiber fabric, and glass cloth.

[0226] The aforementioned foil-like support member is made by forming a metal raw material into a thin film, and examples include aluminum foil and copper foil.

[0227] The porous support member has a porous structure made from organic, inorganic, or metal materials, and examples include porous organic materials (e.g., polyurethane foam), porous inorganic materials (e.g., zeolite sheets), and porous metal materials (e.g., porous metal sheets, porous aluminum sheets).

[0228] The thickness of the support member is not particularly limited and may be, for example, 0.1 to 100 μm or 1 to 50 μm.

[0229] The aforementioned thermal insulation material can also be applied to applications such as thermal insulation, heat retention, or non-combustible materials in the construction, aerospace, automotive, battery, home appliance, semiconductor, and industrial equipment sectors.

[0230] The present invention will be described in detail below with reference to the following examples. However, the following examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples.

[0231] Examples [Example 1] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:6, and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an aqueous HCl solution was added to bring the pH of the silica precursor solution to approximately 3, and the mixture was stirred for more than 2 hours to produce a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:4 with the hydrated TEOS solution. A catalytic sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. 33.3 L of this catalytic sol was packed into an impregnation tank, and then passed through a fiber (glass fiber mat, 5 mm) as a substrate to allow the catalytic sol to permeate the fiber, with the catalytic silica sol impregnating the fiber mat in a volume ratio of 0.6:1 (catalyzed silica sol:fiber). The fiber, impregnated with the catalytic sol after passing through the impregnation tank, was gelled for 10 minutes while passing on a conveyor belt at a constant speed. During this process, the ambient temperature on the conveyor belt was maintained at 35°C. Next, the gelled wet gel composite was aged with 10% by volume of a solution of 2.9% by weight of methyltriethoxysilane (MTES) diluted in 10% by weight ethanol as a maturation solution, and aged at 75°C for 1 hour. After aging, 90% by volume of a hexamethyldisilazane (HMDS) / ethanol solution (5:95 volume ratio) was added to the aged wet gel composite as a surface modifier, and surface modification was performed at 75°C for 4 hours. Next, the silica wet gel was placed in a 7.2 L supercritical fluid extractor and CO2 was injected. Next, the temperature inside the extractor was raised to 70°C over 1 hour and 20 minutes. Once 70°C and 150 bar were reached, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, and then the CO2 injection was stopped for 20 minutes. This process was repeated four times. Ethanol was recovered through the lower end of the separator during the CO2 injection and discharge. Next, the CO2 was vented for 2 hours to produce a hydrophobic silica aerogel composite.

[0232] [Example 2] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:6, and adding ethanol in a weight ratio of 1:1 with the TEOS. To promote the hydrolysis of the silica precursor solution, an aqueous HCl solution was added to bring the pH of the silica precursor solution to approximately 3, and the mixture was stirred for more than 2 hours to produce a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:3 to the hydrated TEOS solution. A catalytic sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. 33.3 L of this catalytic sol was packed into an impregnation tank, and then passed through a fiber (glass fiber mat, 5 mm) as a substrate to allow the catalytic sol to permeate the fiber. The catalytic silica sol was impregnated into the fiber mat in a volume ratio of 0.6:1 (catalyzed silica sol:fiber). The fiber, impregnated with the catalytic sol after passing through the impregnation tank, was gelled for 10 minutes while passing on a conveyor belt at a constant speed. During this process, the ambient temperature on the conveyor belt was maintained at 35°C. Next, the gelled wet gel composite was aged at 75°C for 1 hour. A solution of 2.9% by weight of methyltriethoxysilane (MTES) diluted in 10% by weight ethanol was added to the wet gel composite at a rate of 109% by volume, based on the volume of the wet gel composite. A solution of 2% by volume of trimethylethoxysilane (TMES) diluted in ethanol was added to the aged wet gel composite at a rate of 90% by volume, based on the volume of the wet gel composite, and surface modification was performed at 75°C for 12 hours. Next, the silica wet gel was placed in a 7.2L supercritical fluid extractor and CO2 was injected. The temperature inside the extractor was then raised to 70°C over 1 hour and 20 minutes. Once 70°C and 150 bar were reached, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, and the state was maintained with CO2 injection stopped for 20 minutes. This process was repeated four times. Ethanol was recovered through the lower end of the separator during the injection and discharge of CO2. Next, the CO2 was discharged for 2 hours to produce a hydrophobic silica aerogel composite.

[0233] [Example 3] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:5, and adding ethanol in a weight ratio of 1:1 with the TEOS. To promote the hydrolysis of the silica precursor solution, an aqueous HCl solution was added to bring the pH of the silica precursor solution to approximately 3, and the mixture was stirred for more than 2 hours to produce a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:5 to the hydrated TEOS solution. A catalytic sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. 33.3 L of this catalytic sol was packed into an impregnation tank, and then passed through a fiber (glass fiber mat, 10 mm) as a substrate to allow the catalytic sol to permeate the fiber, ensuring that the catalytic silica sol impregnated the fiber mat in a volume ratio of 1:1 (catalyzed silica sol:fiber). The fiber, impregnated with the catalytic sol after passing through the impregnation tank, was gelled for 10 minutes while passing at a constant speed on a conveyor belt. During this process, the ambient temperature on the conveyor belt was maintained at 40°C. Next, the gelled wet gel composite was aged with 10% by volume of a solution of 2.9% by weight of methyltriethoxysilane (MTES) diluted in 10% by weight ethanol as a maturation solution, and aged at 75°C for 1 hour. After aging, 90% by volume of a hexamethyldisilazane (HMDS) / ethanol solution (5:95 volume ratio) was added to the aged wet gel composite as a surface modifier, and surface modification was performed at 75°C for 4 hours. Next, the silica wet gel was placed in a 7.2 L supercritical fluid extractor and CO2 was injected. Next, the temperature inside the extractor was raised to 70°C over 1 hour and 20 minutes. Once 70°C and 150 bar were reached, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, and then the CO2 injection was stopped for 20 minutes. This process was repeated four times. Ethanol was recovered through the lower end of the separator during the CO2 injection and discharge. Next, CO2 was discharged over 2 hours to produce a hydrophobic silica aerogel composite.

[0234] [Example 4] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:6, and adding ethanol in a weight ratio of 1:1 with the TEOS. To promote the hydrolysis of the silica precursor solution, an aqueous HCl solution was added to bring the pH of the silica precursor solution to approximately 3, and the mixture was stirred for more than 2 hours to produce a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:3 to the hydrated TEOS solution. A catalytic sol was prepared by adding a base catalyst solution (5 wt% aqueous NaOH solution) in a volume ratio of 99:1 with the silica sol. 33.3 L of this catalytic sol was packed into an impregnation tank, and then passed through a fiber (glass fiber mat, 10 mm) as a substrate to allow the catalytic sol to permeate the fiber, ensuring that the catalytic silica sol impregnated the fiber mat in a volume ratio of 1:1 (catalyzed silica sol:fiber). The fiber, impregnated with the catalytic sol after passing through the impregnation tank, was gelled for 10 minutes while passing at a constant speed on a conveyor belt. During this process, the ambient temperature on the conveyor belt was maintained at 40°C. Next, the gelled wet gel composite was aged at 75°C for 1 hour. A solution of 2.9% by weight methyltriethoxysilane (MTES) diluted in 10% by weight ethanol was added to the wet gel composite at a rate of 109% by volume, based on the volume of the wet gel composite. A solution of 2% by volume trimethylethoxysilane (TMES) diluted in ethanol was added to the aged wet gel composite as a surface modifier at a rate of 90% by volume, based on the volume of the wet gel composite. Surface modification was then performed at 75°C for 12 hours. Next, the silica wet gel was placed in a 7.2L supercritical fluid extractor and CO2 was injected. The temperature inside the extractor was then raised to 70°C over 1 hour and 20 minutes. Once 70°C and 150 bar were reached, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, and the state was maintained with CO2 injection stopped for 20 minutes. This process was repeated four times. Ethanol was recovered through the lower end of the separator during the injection and discharge of CO2. Next, the CO2 was discharged for 2 hours to produce a hydrophobic silica aerogel composite.

[0235] [Example 5] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:6, and adding ethanol in a weight ratio of 1:1 with the TEOS. To promote the hydrolysis of the silica precursor solution, an aqueous HCl solution was added to bring the pH of the silica precursor solution to approximately 3, and the mixture was stirred for more than 2 hours to produce a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:3 to the hydrated TEOS solution. A catalytic sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. 33.3 L of this catalytic sol was packed into an impregnation tank, and then passed through a fiber (glass fiber mat, 5 mm) as a substrate to allow the catalytic sol to permeate the fiber. The catalytic silica sol was impregnated into the fiber mat in a volume ratio of 0.6:1 (catalyzed silica sol:fiber). The fiber, impregnated with the catalytic sol after passing through the impregnation tank, was gelled for 10 minutes while passing on a conveyor belt at a constant speed. During this process, the ambient temperature on the conveyor belt was maintained at 35°C. After gelation was complete, the mixture was stabilized at room temperature (25°C) for 10 minutes, followed by primary aging in a 70°C oven for 50 minutes. Next, a solution of 2.9% by weight of methyltriethoxysilane (MTES) diluted in 10% by weight ethanol was prepared and added to the gelled wet gel complex at a volume of 109% based on the wet gel complex, followed by secondary aging in a 75°C oven for 1 hour. To the aged wet gel complex, a solution of trimethylethoxysilane (TMES) diluted in ethanol (2 vol%) was added as a surface modifier at a volume of 90% based on the wet gel complex. After adding a volume percentage, surface modification was performed at 75°C for 6 hours. Next, the silica-wet gel was placed in a 7.2 L supercritical fluid extractor and CO2 was injected. Then, the temperature inside the extractor was raised to 70°C over 1 hour and 20 minutes. Once 70°C and 150 bar were reached, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, and the state was maintained with CO2 injection stopped for 20 minutes. This process was repeated four times. Ethanol was recovered through the lower end of the separator during CO2 injection and discharge. Next, CO2 was discharged over 2 hours to produce a hydrophobic silica aerogel composite.

[0236] [Comparative Example 1] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4, and then adding ethanol in a weight ratio of 1:1 with the TEOS. To promote the hydrolysis of the silica precursor solution, an aqueous HCl solution was added to bring the pH of the silica precursor solution to approximately 2, and the mixture was stirred for more than 2 hours to produce a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:3 to the hydrated TEOS solution. A catalytic sol was prepared by mixing the silica sol with aqueous ammonia (30 wt%) in a volume ratio of 99.5:0.5. 33.3 L of this catalytic sol was packed into an impregnation tank, and then passed through a fiber (glass fiber mat, 10 mm) as a substrate to allow the catalytic sol to permeate the fiber, ensuring that the catalytic silica sol impregnated the fiber mat in a volume ratio of 1:1 (catalyzed silica sol:fiber). The fiber, impregnated with the catalytic sol after passing through the impregnation tank, was gelled for 10 minutes while passing at a constant speed on a conveyor belt. During this process, the ambient temperature on the conveyor belt was maintained at 30°C. Next, the gelled wet gel composite was left to mature at 25°C for 24 hours. To the matured wet gel composite, 90% by volume of hexamethyldisilazane (HMDS) / ethanol solution (5:95 volume ratio) was added based on the volume of the wet gel composite as a surface modifier, and then surface modification was carried out at a temperature of 75°C for 4 hours. Next, the silica wet gel was placed in a 7.2L supercritical fluid extractor and CO2 was injected. Next, the temperature inside the extractor was raised to 70°C over 1 hour and 20 minutes. Once 70°C and 150 bar were reached, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, and the process of stopping CO2 injection for 20 minutes was repeated four times. Ethanol was recovered through the lower end of the separator during CO2 injection and discharge. Next, CO2 was discharged over 2 hours to produce a hydrophobic silica aerogel composite.

[0237] [Comparative Example 2] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:5, and adding ethanol in a weight ratio of 1:1 to the TEOS. To promote the hydrolysis of the silica precursor solution, an aqueous HCl solution was added to bring the pH of the silica precursor solution to approximately 2, and the mixture was stirred for more than 2 hours to produce a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:3 to the hydrated TEOS solution. A catalytic sol was prepared by mixing the silica sol with aqueous ammonia (30 wt%) in a volume ratio of 99.5:0.5. 33.3 L of this catalytic sol was packed into an impregnation tank, and then passed through a fiber (glass fiber mat, 10 mm) as a substrate to allow the catalytic sol to permeate the fiber. The catalytic silica sol was impregnated into the fiber mat in a volume ratio of 0.4:1 (catalyzed silica sol:fiber). The fiber, impregnated with the catalytic sol after passing through the impregnation tank, was gelled for 10 minutes while passing at a constant speed on a conveyor belt. During this process, the ambient temperature on the conveyor belt was maintained at 25°C. Next, the gelled wet gel composite was aged with 109% by volume of a solution of 2.9% by weight of methyltriethoxysilane (MTES) diluted in 10% by weight ethanol as a maturation solution, and aged at 75°C for 1 hour. After aging, 90% by volume of a hexamethyldisilazane (HMDS) / ethanol solution (5:95 volume ratio) was added to the aged wet gel composite as a surface modifier, and surface modification was performed at 75°C for 4 hours. Next, the silica wet gel was placed in a 7.2 L supercritical fluid extractor and CO2 was injected. Next, the temperature inside the extractor was raised to 70°C over 1 hour and 20 minutes. Once 70°C and 150 bar were reached, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, and then the CO2 injection was stopped for 20 minutes. This process was repeated four times. Ethanol was recovered through the lower end of the separator during the CO2 injection and discharge. Next, CO2 was discharged over 2 hours to produce a hydrophobic silica aerogel composite.

[0238] [Comparative Example 3] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:3, and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, acid was added to bring the pH of the silica precursor solution to approximately 3, and the mixture was stirred for more than 2 hours to produce a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:6 with the hydrated TEOS solution. A catalytic sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. The catalytic sol was impregnated into a fiber (glass fiber mat, 5 mm) as a substrate, with the catalytic silica sol impregnating the fiber in a volume ratio of 0.6:1 (catalyzed silica sol:glass fiber mat) relative to the volume of the glass fiber mat, and gelation was performed after 10 minutes to produce a wet gel composite. The fiber impregnated with the catalytic sol passed through the impregnation tank and gelled for 10 minutes while passing on a conveyor belt at a constant speed. During this process, the ambient temperature on the conveyor belt was maintained at 25°C. Next, the gelled wet gel composite was aged with 109% by volume of a solution of 2.9% by weight of methyltriethoxysilane (MTES) diluted in 10% by weight ethanol as a maturation solution, and aged at 75°C for 1 hour. After aging, 90% by volume of a hexamethyldisilazane (HMDS) / ethanol solution (5:95 volume ratio) was added to the aged wet gel composite as a surface modifier, and surface modification was performed at 75°C for 4 hours. Next, the silica wet gel was placed in a 7.2 L supercritical fluid extractor and CO2 was injected. Next, the temperature inside the extractor was raised to 70°C over 1 hour and 20 minutes. Once 70°C and 150 bar were reached, CO2 was injected and discharged at a rate of 0.5 L / min for 20 minutes, and then the CO2 injection was stopped for 20 minutes. This process was repeated four times. Ethanol was recovered through the lower end of the separator during the CO2 injection and discharge. Next, CO2 was discharged over 2 hours to produce a hydrophobic silica aerogel composite.

[0239] [Experimental Example 1] Measurement of density and stomatal size distribution 1. Density For each silica aerogel composite produced in each Example and Comparative Example, five test specimens of 10 cm × 10 cm size were prepared, the weight of each was measured, and the thickness of the test specimens was measured using an HFM436 apparatus manufactured by NETZSCH. The density was calculated from the measured weight, thickness and size, the average density of the five test specimens was determined as the final density, and the results are shown in Table 1 below.

[0240] 2. Volume ratio (%) of effective pores having a pore diameter of 30 nm or less Each silica aerogel composite produced in each Example and Comparative Example was analyzed for nitrogen adsorption / desorption amount at partial pressure (0.11<p / p0<1) using an ASAP 2010 apparatus manufactured by Micromeritics, to measure the specific surface area, pore volume, and pore diameter. The volume ratio of pores (effective pores) having a pore diameter within the numerical range of 30 nm or less was calculated from the measured pore volume, and the results are shown in Table 1 below.

[0241] [Table 1]

[0242] [Experimental Example 2] SAXS Analysis of Aerogel Particles To perform small-angle X-ray diffraction (SAXS) analysis on the aerogel particles contained in the aerogel composites obtained in Examples 1 to 5 and Comparative Examples 1 to 3, first, aerogel composites of Examples 1 to 5 and Comparative Examples 1 to 3 were prepared in a size of 60 cm x 12 cm. After placing each aerogel composite in a sealable vinyl container, the container was repeatedly shaken up and down to intentionally induce the detachment of the aerogel powder (aerogel particles). The fibrous substrates mixed in the obtained aerogel powder, which were visible to the naked eye, were removed with tweezers. Next, for a more precise analysis, in order to further remove the fibrous substrates mixed in the detached powder, aerogel powder was placed in a 100 ml vial, and distilled water was added so that the weight ratio of powder to distilled water was approximately 1:130, and the vial was shaken vigorously up and down 50 times. Next, the fibrous substrates that had settled at the bottom of the vial were removed, and any clumps formed by the aggregation of the fibrous substrates and aerogel powder were also removed. Only aerogel powder that did not form aggregates was carefully collected and dried at 120°C for 1 hour. 10 mg of the final aerogel powder was taken and subjected to the following small-angle X-ray scattering (SAXS) analysis. A Xenocs Xeuss2.0 X-ray scattering system was used, with the aerogel powder sample placed approximately 2.5 m away from the detector and X-rays incident on it. A Pilatus3 300K (2D detector) was used as the detector. The scattered 2D diffraction pattern was obtained as an image, and this was calibrated using the sample-to-detector distance obtained with a standard sample. The scattering intensity I(q) was converted to a value for the scattering wavenumber Q using circular averaging, and a logarithmic graph of the scattering intensity I(q) against the scattering wavenumber Q was obtained. Table 2 shows the gradient obtained by calculating the change in scattering intensity due to wavenumber changes of 0.015 / Å to 0.035 / Å in the small-angle X-ray diffraction (SAXS) graphs obtained for the aerogel powders of Examples 1 to 5 and Comparative Examples 1 to 3. Linear regression was obtained by the least squares method considering all measured values ​​(q, Intensity I(q)) in the wavenumber range of 0.015 / Å to 0.035 / Å. The gradient obtained is shown in Table 2.The small-angle X-ray diffraction (SAXS) graphs obtained for the aerogel powders of Examples 1 and 3, and Comparative Examples 1 and 2, are shown in Figures 1 and 2. However, in order to confirm whether it is possible to analyze aerogel particles located within the fiber substrate even when performing small-angle X-ray diffraction (SAXS) on the aerogel composite rather than the detached aerogel powder, a 1cm × 1cm square specimen was obtained from the center of the aerogel composite of Example 1, and the graph obtained by performing small-angle X-ray diffraction (SAXS) analysis using the same method is also shown in Figure 1.

[0243] [Table 2]

[0244] As can be seen from Table 2 and Figures 1 and 2, the aerogel powders derived from the aerogel composites of Examples 1 to 5 according to the present invention can be confirmed to have gradients measured in the wavenumber range of 0.015 / Å to 0.035 / Å in the small-angle X-ray scattering (SAXS) graph that belong to the range of -2.80 to -2.20. This indicates that the aerogel powders of Examples 1 to 5 according to the present invention contain a high proportion of secondary aerogel particles having a flattened spherical disk-like structure in the central part, while the aerogel powders of Comparative Examples 1 to 3 contain a high proportion of secondary aerogel particles that are closer to two-dimensional disk-like structures (i.e., disk-like structures with a flat central part). Furthermore, as can be seen in Figure 1, the small-angle X-ray scattering (SAXS) graph for the aerogel powder of Example 1 shows a slope of -2.22, while the small-angle X-ray scattering (SAXS) graph for the aerogel composite specimen of Example 1 shows a slope of -2.25 for the same wavenumber range. This indicates that information about the shape of the aerogel particles contained within can also be obtained from small-angle X-ray scattering (SAXS) analysis of the aerogel composite itself.

[0245] [Experimental Example 3] Measurement of recovery rate and thermal reflux rate of aerogel composite after compression. The aerogel composites obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were manufactured in a rectangular shape with dimensions of 60 cm x 12 cm. However, in the following experiments, considering the specifications of the measurement equipment, each aerogel composite was cut in half horizontally to obtain two specimens measuring 30 cm x 12 cm. These specimens were then rearranged so that they were adjacent to each other, resulting in a specimen measuring 30 cm x 24 cm, and these specimens were then analyzed.

[0246] 1. Compression recovery rate As described above, the aerogel composite specimens obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were pressed for 10 minutes at each pressure condition using a QMESYS QM900A-15T press. The thickness of the aerogel composite was measured using a Netzsch HFM436 press before pressing and 1 hour after pressing was completed. The compression recovery rate was calculated according to Equation 2 below, and the results are shown in Table 3. However, the pressure values ​​shown in Table 3 below represent the pressure applied per unit area of ​​the specimen, and are calculated by multiplying the cylinder area of ​​the press equipment by the set pressure value and dividing by the area of ​​the specimen obtained as shown in Equation 3. The cylinder radius of the QM900A-15T press equipment used in this experiment was 6.25 cm, and the cylinder size was 12.5 cm. [Formula 2] Compression recovery force (%) = {(thickness of the cross-section of the aerogel composite after compression) / (thickness of the cross-section of the aerogel composite before compression)} × 100 [Formula 3] Actual pressure value = (radius of the cylinder inner diameter of the press equipment (cm) × radius of the cylinder inner diameter of the press equipment (cm) × 3.14 × set pressure value) / (area of ​​the test piece (cm) 2 ))

[0247] 2. Heat transmission coefficient After conducting the experiment using the same method as described in 1. above, the thermal conductivity of the aerogel composite was measured using Netzsch HFM436 equipment before compression and one hour after compression was completed. The heat recirculation coefficient was then calculated, and the rate of increase in the heat recirculation coefficient compared to before compression was evaluated. The results are shown in Table 4 below.

[0248] In addition, to confirm the degree of change in thermal transmittance before and after compression, after compressing at pressures of no compression (0 bar), 3 bar, 9 bar, and 24 bar, the average value (b) of the measured thermal transmittance was calculated, and as shown in Equation 4 below, A, which is the value obtained by dividing the difference between the thermal transmittance (a) measured after compression at each pressure of 0 bar, 3 bar, 9 bar, and 24 bar and the average value (b) of these thermal transmittances by the average value (b) of the thermal transmittance, was calculated, and the results are shown in Table 5. [Equation 4] {(Thermal transmittance (a) before and after compression) - (Average value (b) of thermal transmittance before and after compression)} = (Average value (b) of thermal transmittance before and after compression) × A

[0249] In addition, to confirm the degree of change in thermal transmittance after compression, after compressing at pressures of 3 bar, 9 bar, and 24 bar, the average value (d) of the measured thermal transmittance was calculated, and as shown in Equation 5 below, B, which is the value obtained by dividing the difference between the thermal transmittance (c) measured after compression at the pressure of 3 bar, 9 bar, or 24 bar and the average value (d) by the average value (d) of the thermal transmittance, was calculated, and the results are shown in Table 6. [Equation 5] (Thermal transmittance (c) after compression - Average value (d) of thermal transmittance after compression) = (Average value (d) of thermal transmittance after compression) × B

[0250] Each of the result values shown in Tables 3 to 6 below is rounded off to 2 decimal places by rounding the 3rd decimal place.

[0251] [Table 3A] [Table 3B]

[0252] [Table 4A] [Table 4B]

[0253] [Table 5A] [Table 5B]

[0254] [Table 6A] [Table 6B]

[0255] As can be seen from Tables 4 to 6 above, the aerogel composites of Examples 1 to 5 produced by the present invention were found to have a higher compression recovery rate compared to the aerogel composites of Comparative Examples 1 to 3. The degree of increase in the thermal transmittance of the aerogel composite after compression compared to before compression was low, and even when compressed to various pressure values ​​from low to high during compression, the degree of change in thermal transmittance was small, confirming that the thermal insulation performance was maintained at an excellent level. From these results, it can be confirmed that the aerogel composite of the present invention is excellent in both the elasticity, flexibility and strength of the pores, and has excellent recovery power even after high-pressure compression, thereby preventing a rapid decrease in thermal insulation performance due to pore destruction, especially the destruction of pores with a size of 30 nm or less, and thus the thermal insulation performance is excellently supported even after compression.

[0256] Although specific parts of the present invention have been described in detail, it is clear to those with ordinary skill in the art that such specific technologies are merely preferred examples and do not limit the scope of the present invention. Therefore, the substantial scope of the present invention is defined by the attached claims and their equivalents. [Industrial applicability]

[0257] This invention relates to an aerogel composite that can maintain an excellent level of thermal insulation without a significant decrease in thermal insulation even when compressed by external pressure due to various causes, and to its application as a thermal insulation material. The thermal insulation material can also be applied to batteries, electronic devices, automobiles, work equipment, or structures.

Claims

1. An aerogel composite comprising a fibrous substrate and an aerogel containing a plurality of open pores, wherein the aerogel contains a plurality of silica aerogel particles, In a small-angle X-ray scattering (SAXS) graph showing the scattering intensity against wave number for the aerogel particles in a logarithmic manner, the slope in the wave number range of 0.015 / Å to 0.035 / Å is -2.80 to -2.20, wherein the aerogel composite is characterized by this graph.

2. The aerogel composite according to claim 1, wherein the small-angle X-ray scattering graph is for silica aerogel particles detached from the aerogel composite.

3. The aerogel composite according to claim 1, wherein the small-angle X-ray scattering graph is for silica aerogel particles within the aerogel composite.

4. The aerogel composite according to claim 1, wherein when pressures of 3 bar, 9 bar, and 24 bar are applied horizontally (laterally) to the cross-section of the aerogel composite, the thermal transmittance after compression is 1.8 times or less compared to the thermal transmittance before compression.

5. The aerogel composite according to claim 1, wherein when pressures of 3 bar, 9 bar, and 24 bar are applied horizontally (laterally) to the cross-section of the aerogel composite, the thermal transmittance after compression is more than 1 and less than or equal to 1.8 times the thermal transmittance before compression.

6. The aerogel composite according to claim 1, wherein the thermal transmittance before and after compression satisfies the following equation 4: [Formula 4] {(Thermal transmittance before and after compression (a)) - (Average thermal transmittance before and after compression (b))} = (Average thermal transmittance before and after compression (b)) × A In the above formula 4, The thermal transmittance before and after compression (a) refers to the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) at 0 bar, 3 bar, 9 bar, or 24 bar relative to its cross-section. The average value of the thermal transmittance before and after compression (b) represents the thermal transmittance of the unpressurized aerogel composite and the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with compression values ​​of 3 bar, 9 bar, and 24 bar relative to the cross-section. A is between -0.40 and +0.

40.

7. The aerogel composite according to claim 1, wherein the thermal transmittance before and after compression satisfies the following equation 4: [Formula 4] {(Thermal transmittance before and after compression (a)) - (Average thermal transmittance before and after compression (b))} = (Average thermal transmittance before and after compression (b)) × A In the above formula 4, The thermal transmittance (a) before and after compression refers to the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) at 0 bar, 3 bar, or 9 bar relative to its cross-section. The average value of the thermal transmittance before and after compression (b) represents the thermal transmittance of the unpressurized aerogel composite and the average value of the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with compression values ​​of 3 bar and 9 bar relative to the cross-section. A is between -0.23 and 0.

23.

8. The aerogel composite according to claim 1, wherein the thermal transmittance obtained after compressing the aerogel composite horizontally (laterally) with pressures of 3 bar, 9 bar, and 24 bar with respect to the cross-section of the aerogel composite satisfies the following formula 5: [Formula 5] {(Compressed heat transfer coefficient (c) - Average heat transfer coefficient after compression (d))} = (Average heat transfer coefficient after compression (d)) × B In the above formula 5, The thermal transmittance after compression (c) refers to the thermal transmittance obtained after compressing the aerogel composite with a pressure of 3 bar, 9 bar, or 24 bar in the horizontal direction (lateral direction) relative to the cross-section. The average value of the thermal transmittance after compression (d) refers to the average value of the thermal transmittance obtained after compressing the aerogel composite by applying pressures of 3 bar, 9 bar, and 24 bar in the horizontal direction (lateral direction) relative to the cross-section of the aerogel composite. The aforementioned B is between -0.30 and +0.

30.

9. The aerogel composite according to claim 1, wherein the rate of change (C) of the thermal transmittance after compression per unit applied pressure, represented by the following formula 6, is -0.15 to +0.15: [Formula 6] C = {(Thermal transmittance after compression at pressure x - Thermal transmittance after compression at pressure y)} / (x - y) In the above formula 6, x and y are either independently 3 bar or 24 bar, or have different pressure values.

10. When pressures of 3 bar, 9 bar, and 24 bar are applied horizontally (laterally) to the cross-section of the aerogel composite, the compression recovery force represented by the following formula 2 is 60% or more, as described in claim 1: [Formula 2] Compression recovery force (%) = {(thickness of the cross-section of the aerogel composite after compression) / (thickness of the cross-section of the aerogel composite before compression)} × 100

11. The aerogel composite according to claim 1, wherein the aerogel contains pores with a pore diameter of 30 nm or less in an amount of 30% to 45% of the pore volume of the skeletal structure.

12. The aerogel composite according to claim 1, wherein the aerogel comprises silica, methylsilylated silica, dimethylsilylated silica, trimethylsilylated silica, or a mixture thereof.

13. The aerogel composite according to claim 1, wherein the silica aerogel particles include particles in which a plurality of aerogel particles with a particle size greater than 0 and less than 5 nm are aggregated or bound together.

14. The aerogel composite according to claim 13, wherein the average particle size of the aggregated or bound particles is 5 to 2000 nm.

15. The aerogel composite according to claim 1, wherein the thickness of the aerogel composite is 0.5 mm to 20 mm.

16. The density of the aerogel composite is 0.05 g / cm³. 3 ~0.50g / cm 3 The aerogel composite according to claim 1.

17. The aerogel composite has a compressive strength of 20 kPa to 80 kPa and a tensile strength of 30 N / cm² at 10% deformation. 2 ~60N / cm 2 The aerogel composite according to claim 1.

18. A thermal insulation member comprising the aerogel composite according to any one of claims 1 to 17.

19. The thermal insulation member according to claim 18, further comprising a support member located on at least one of the upper and lower surfaces of the aerogel composite.